A critical review on microalgae-driven wastewater treatment: Dual focus on high-value bioproducts recovery and emerging contaminants removal - Shuli Liu; Jiajun Hua; Yuhong Zhang; Yatong Gao; Xiaohong Han; Yali Liu; Glen T. Daigger; Qi Li; Ning Guo; Zhixin Song; Peng Zhang; Xiane Zhang; et al. (Journal of Environmental Sciences, 2026)

Clinical outcomes of patients with brain metastases from primary esophageal cancer - Bianca Nolde-Lopez; Christina K. Cramer; Scott Isom; Anthony Naquin; Caio M.S.P. Rocha Lima; Ravi K. Paluri; Jimmy Ruiz; Fei Xing; Christopher T. Whitlow; Stephen B. Tatter; Adrian W. Laxton; Jaclyn J. White; et al. (Next Research, 2026)

A comparative analysis of regulatory frameworks and their market impacts on health functional foods: perspectives from South Korea, Canada, the United States, and China - Da-Eun Min; Dal Eum Han; Kwonsoo Kang; Ke Ding; Guangpeng Xu; Mi-Young Lee; Dong Sung An; Nayon Hur; Jin Man Kim; Ji Youn Hong; Bok Kyung Han; Martin J. T. Reaney; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Climate change during the early Middle Jurassic: Evidence from coal-bearing strata of the Ordos Basin - Nian-De Shang; Jing-Jing Liu; Shi-Feng Dai; Ian T. Graham; Qiu-Chan Han; Rong-Kun Jia; Jia-Wei Feng; Meng-Da Yao; Yan Wang (Palaeoworld, 2026)

Extraction and characterization of bioactive oligosaccharides from pulse processing byproducts using subcritical water extraction: a proof-of-concept study - Jasmin S. Yang; T. Truc K. Pham; Andrea J.C. Tam; Han Peng; Tássia B. Pessato; You-Tae Kim; Peter J. Russell; Zhiliang Fan; David A. Mills; Daniela Barile; Juliana Maria Leite Nobrega de Moura Bell (Food Chemistry, 2026)

Explicit dynamic modeling of finite-length spherical joints in FRP bending-active gridshells: Formulation and validation - E.L. Xie; T. Jiang; Z.Y. Xia; Z.T. Han; S. Jin (Engineering Structures, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Synergistic oxygen intermediate spillover in Pt3Co-PtCo dual-phase intermetallics for enhanced oxygen reduction kinetics - Uhyeok Son; Jong Yoon Lee; Hye Jeong Joe; Gi Won Lee; Seunggyun Han; Seon-yeong Lee; Jeong Hee Lee; Jae-Hyun Park; Sung Jong Yoo; Kug-Seung Lee; Seok Ki Kim; Joseph T. Hupp; et al. (Chemical Engineering Journal, 2026)

Feasibility of home-based, remotely delivered exercise training to improve physical function in older sepsis survivors: a pilot randomized controlled trial - Yi Lin; Rola S. Zeidan; Rezvan Ghaderpanah; Margaret K. Ohama; Min-Han Jung; Naveen Baskaran; Juan Sarmiento Delgado; Stephen D. Anton; Barbara K. Smith; Christiaan Leeuwenburgh; Fang-Chi Hsu; Philip A. Efron; et al. (GeroScience, 2026)
Sepsis survivors frequently experience post-discharge physical function decline and encounter logistical barriers to participation in traditional outpatient rehabilitation. This pilot study examined the feasibility, safety, and preliminary efficacy of a remotely delivered, home-based exercise program on physical function in older sepsis survivors. In this single-blinded, randomized controlled trial (RCT), sepsis survivors aged ≥ 55 years were randomized to (a) 12 weeks of avatar-guided, progressive exercise training group (EX) or (b) a standard care control group (CO). Primary outcomes were feasibility (retention, adherence) and safety (adverse events), whereas secondary outcomes were changes in the 30-s Sit-to-Stand (30SSTS), 4-Stage Balance Test (4SBT), Timed Up-and-Go (TUG) tests, and Eastern Cooperative Oncology Group/Zubrod's (ECOG/Zubrod) performance status score. Twenty-one participants were randomized to either EX ( n = 10, mean age = 69.6 ± 8.5 years, 40% females) or CO ( n = 11, mean age = 72.3 ± 7.9 years, 45% females). Mean retention was 95% and adherence to exercise training was 76%. Thirty-four adverse events (AEs) occurred (EX = 11; CO = 16; consented but not randomized = 7 events), including four serious AEs that were unrelated to the study. The EX group showed trends toward improvements in lower-extremity strength (30SSTS: 1.14 ± 2.91 repetitions, Cohen’s d = 0.393) and balance (4SBT: 5.07 ± 4.75 s, d = 1.07), whereas the CO group showed no change in balance on the 4SBT (0.01 ± 4.38 s, d = 0.003) and trends toward decline in lower-extremity strength on the 30SSTS (− 0.88 ± 0.99 repetitions, d = − 0.883). TUG performance showed modest trends toward reductions in completion time in both groups (EX: − 1.42 ± 6.58 s, d = − 0.216; CO: − 1.27 ± 2.73 s, d = − 0.466). ECOG/Zubrod scores showed a modest trend toward improvement in the EX group subset. This pilot RCT demonstrated that a 12-week, remotely delivered exercise program was safe and feasible for older sepsis survivors and showed preliminary signals of positive change in lower-extremity strength, balance, and functional status, which warrants testing efficacy in an adequately powered Phase IIb RCT. ClinicalTrials.gov NCT05568511.

Geothermal resource identification in Australia using shallow groundwater temperature data - Y. Han; L. T. White; W. G. P. Kumari; T. Murray (Australian Journal of Earth Sciences, 2026)

A practical workflow for fixation and autofluorescence reduction in correlative light and electron microscopy of postmortem human brain tissue - Ha-Eon Lee; Hong Lim Kim; Ara Cho; Do-Gyun Kim; Min-Jin Park; Yuna Oh; Yong Soo Park; Rafael T. Han; Mun‑Yong Lee; Tae-Ryong Riew (Tissue and Cell, 2026)

Does soil inoculation truly steer the composition of native soil communities? - Yuhui Li; Yingbin Li; Xu Han; Qi Li; T. Martijn Bezemer (Soil Biology and Biochemistry, 2026)

Impacts of Cycle Time on N Removal Performance, Microbial Community and N Cycling Pathways in Domestic Wastewater Treated by Sequencing Batch Biofilm Reactor (SBBR) - Shuli Liu; Yuhong Zhang; Miao Zhou; Yatong Gao; Xiaohong Han; Glen T. Daigger; Jia Kang; Xiane Zhang (Water, Air, & Soil Pollution, 2026)

Impact of age and rurality on colorectal cancer outcomes in the United States - Caitlyn Grunert; Meng-Han Tsai; Charles R. Rogers; Sydney Howard; Rachel Hogg-Graham; Courtney Martin; Darwin Conwell; Adetunji T. Toriola; Avinash Bhakta; Justin X. Moore (Cancer Causes & Control, 2026)
Background While overall colorectal cancer (CRC) rates have declined in the United States (U.S.), early-onset CRC (EO-CRC), diagnosed before age 50, has increased. Rural U.S. residents face higher CRC incidence than non-rural counterparts. We aimed to examine the relationship between age at diagnosis and EO-CRC outcomes and whether rurality modify these associations. Methods We analyzed data from 835,907 patients aged 20–79 years in the 2006–2020 SEER Program. Rurality was defined using U.S. Department of Agriculture Rural–Urban Commuting Area (RUCA) codes. Multivariable logistic regression models were used to examine associations between age, rurality, and late-stage CRC diagnosis. Competing-risk regression models were applied to evaluate CRC-specific mortality, accounting for non–CRC deaths. Patients aged 50–59 years residing in non-rural areas served as the reference group for joint age–rurality analyses. All models adjusted for demographic, socioeconomic, clinical, and treatment factors. Results Patients aged 30–39 (aOR: 1.49, 95% CI: 1.44–1.54) and 40–49 (aOR: 1.43, 95% CI: 1.40–1.46) had significantly higher odds of late-stage CRC compared with those aged 50–59, with the strongest associations observed among non-rural patients aged 30–39 (aOR: 1.52, 95% CI: 1.46–1.58). In competing-risk models, rural patients were at higher CRC-specific mortality across all age groups, with relative hazard increases ranging from 8% in older adults (70-79) to 21% in younger adults (20-29) compared with their non-rural counterparts. Conclusion Adults aged 30–49 had higher odds of late-stage CRC than those 50–59, especially in non-rural areas. Rural residence was associated with higher CRC-specific mortality across all ages. Overall, age more strongly predicted late-stage diagnosis, while rurality more strongly predicted mortality. Earlier detection and improved clinical awareness in younger adults may reduce advanced-stage disease and CRC deaths.

Brain macrostructure correlates of financial altruism in older adults without dementia - Laura Fenton; Gali H. Weissberger; Lauren E. Salminen; Anya Samek; Daisy T. Noriega-Makarskyy; Cassidy P. Molinare; Jordan Williams; Emma Oyen; Paige Kim; Jenna Axelrod; Laura Mosqueda; Hussein Yassine; et al. (Brain Imaging and Behavior, 2026)
Greater financial altruism (i.e., the tendency to give money to an anonymous individual) has been previously associated with poorer performance on neuropsychological tests sensitive to cognitive changes occurring in early Alzheimer’s disease (AD). While these findings provide initial support for the idea that financial altruism may be associated with early AD-related brain changes, no study has used MRI to investigate structural brain correlates of financial altruism in older adults. To address this gap in the literature, the current study investigated associations between brain macrostructure and financial altruism in 101 older adults free from dementia (mean age = 68.45±7.15, mean education = 16.61±2.14, 76% female, 73% White) using a high-field 7 Tesla MRI. Results revealed no significant associations between financial altruism and a priori regions of interest (entorhinal cortex, hippocampus, ventromedial prefrontal cortex, dorsolateral prefrontal cortex, and temporoparietal junction) in the entire sample. However, there was a significant interaction between financial altruism and income, whereby greater financial altruism was associated with lower hippocampal volume in those with a reported income below $100,000. Collectively these results suggest that financial altruism in the context of lower income, but not financial altruism in general, may reflect suboptimal brain aging, and perhaps greater risk of conversion to AD.

Bimetallic synergism-driven Au0.75Pt0.25 nanoparticles-modified SnO2 heterojunction nanostructures for ultrasensitive detection of carbonate-based electrolyte leakage gases towards battery safety applications - PeiJiang Cao; LinLong Qu; YuWei Li; Fang Jia; YuXiang Zeng; DeLiang Zhu; ChunFeng Wang; Shun Han; Ming Fang; XinKe Liu; WenJun Liu; Sachin T. Navale (Chemical Engineering Journal, 2026)

Laboratory observations of long wave inundation of shorelines in the shadow of islands - John T. Goertz; Nikos Kalligeris; Sunghoon Han; James M. Kaihatu; Patrick J. Lynett; Costas E. Synolakis (Coastal Engineering, 2026)

Developmental vulnerability to fluoride toxicity: enamel and clearance differences in adolescent versus mature mice - Shohei Yamashita; Motoki Okamoto; Natsumi Fujiwara; Ria Achong-Bowe; Susanne Brueckner; Melanie Mendonca; Nanako Kuriki; Hiroko Harigaya; Juliana Sanches Trevizol; Deana Kukhianidze; Roger Zhong; Marion A. Cooley; et al. (Archives of Toxicology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Not all boxes are equal: Investigation of parameters affecting PM2.5 particle removal by the Corsi-Rosenthal box - Antonio Baratta; Taewon T. Han; Gediminas Mainelis (Journal of Aerosol Science, 2026)

Development of an advanced personal nasal sampler (PNS) to access exposure to bioaerosols - Taewon T. Han; Atila Lima; Dong Ming He; Gary Brewer; Gediminas Mainelis (Journal of Aerosol Science, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Hofmeister-regulated fabrication of piezoelectric β-PVDF membrane: The specific ion effect on the membrane formation, piezoelectric property, and anti-fouling performance - R.D. Hope T. Cayron; Hannah Faye M. Austria; Tsung-Han Huang; Gabriel V. Carballo; Smrutiranjan Nayak; Alvin R. Caparanga; Wei-Song Hung; Kueir-Rarn Lee; Juin-Yih Lai (Chemical Engineering Journal, 2025)

Recovery of siliceous ecosystems promoted Early Silurian climatic cooling - Huan Xu; Bo Ran; Terry T. Isson; Xinyang Chen; Chao Luo; Yi Li; Yiqing Zhu; Tong Sun; Yuyue Han (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Self-powered humidity sensor based on porous Ti₃C₂Tₓ MXene: High sensitivity and fast response for real-world applications - Linh Chi T. Cao; Luqman Hakim; Yuki Nagao; Sakoolkan Boonruang; Shih-Feng Tseng; Shu-Han Hsu (Chemical Engineering Journal, 2025)

Electrochemical membrane bioreactors for wastewater treatment: Mechanisms of membrane fouling control and applications to refractory pollutants - Shuli Liu; Yatong Gao; Xiaohong Han; Jiajun Hua; Yuhong Zhang; Glen T. Daigger; Qi Li; Ning Guo; Xiao Mi; Jia Kang; Peng Zhang (Journal of Environmental Chemical Engineering, 2025)

Provenance analysis of late Pleistocene sediment from IODP site U1477 reveals climate and river basin dynamics in the Zambezi river catchment - Youhong Gao; Hucai Zhang; Xiaonan Zhang; Lizeng Duan; Huayong Li; Ian R. Hall; Sidney R. Hemming; Leah J. LeVay; Junsheng Nie; Xibin Han; S. Barker; M.A. Berke; et al. (Gondwana Research, 2025)

Clean water and energy co-generation via alternative renewables - Xiaochao Fan; Bushra Shakoor; Han Yusen; Shi Ruijing; Yang Mingtao; Li Ziqiang; Naila Arshad; Uzma Ghazanfar; Van-Duong Dao; Jian Zhang; Muhammad Sultan Irshad; Calvyn T. Howells; et al. (Chemical Engineering Journal, 2025)

Porosity-controlled MXene anodes for enhanced rate and long cycle life performance in aqueous proton batteries - Linh Chi T. Cao; Kentaro Aoki; Shu-Han Hsu; Sakoolkan Boonruang; Yuki Nagao (Chemical Engineering Journal, 2025)

Phenotypic Trait Monitoring of Victoria amazonica Plants Using Unmanned Aerial Vehicles - Anjali Rai; Pranav R. T. Peddinti; Byungmin Kim; Sung Soo Han; Seon Joo Park (Journal of the Indian Society of Remote Sensing, 2025)

Synthesis of Population Trends Reveals Seascape‐Wide Reorganisation of Biodiversity From Microalgae to Birds - Anika Happe; Kasper J. Meijer; Jan‐Claas Dajka; Oscar Franken; Holger Haslob; Laura L. Govers; Michael Kleyer; Annebelle C. M. Kok; Lucie Kuczynski; Kertu Lõhmus; Sancia E. T. van der Meij; Han Olff; et al. (Global Change Biology, 2025)
Many monitoring programs aim to understand regional biodiversity patterns in relation to global and regional conservation targets, using either community‐wide biodiversity metrics to describe the community status or trends of pre‐selected “key” species as biodiversity change indicators. However, the former often lacks information on which species are changing, and the latter is heavily skewed towards specific taxa, potentially overlooking changes in other, functionally important taxa. We gathered an extensive set of monitoring data with over 3000 population trends (ranging from 5 to 91 years in duration) for a wide range of taxa across the Wadden Sea. We combined a systematic and quantitative categorization of population trends (weighted vote count) with a meta‐analysis on different taxonomic levels. This allowed the first cross‐taxa synopsis of species declines and increases and determined their directionalities throughout time. Our meta‐analysis showed an overall decrease in population size for fish, zooplankton, and plant species, while birds showed an overall increase. However, these increases mask recent negative trends within specific bird groups since the late 1990s. In contrast, fish populations exhibited declines over the entire monitoring period. Species with declining populations (losers) were phylogenetically related, whereas species with increasing populations (winners) represented various organismal groups. Directionality and onsets of change in population trends were temporally synchronized throughout several groups, such as bivalves, fish, and birds, and may provide warning signals for future local extinctions in these taxa. Our analysis moves beyond typical indicator species by including the entire species inventory of the system. Basal trophic levels of aquatic ecosystems, such as zooplankton and phytoplankton, are often missing from policy assessments but are among the most important organism groups for ecosystem functioning. Here, we show that without additional monitoring effort, a systematic analysis of population trends adds to our understanding of trophic and compositional restructuring of ecosystems.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Performance, mechanism regulation and resource recycling of bacteria-algae symbiosis system for wastewater treatment: A review - Shuli Liu; Zhihui Kong; Haoyi Guo; Yuhong Zhang; Xiaohong Han; Yatong Gao; Glen T. Daigger; Guangming Zhang; Ruihua Li; Yuhao Liu; Peng Zhang; Gangfu Song (Environmental Pollution, 2024)

Revival of cryopreserved larvae from the important aquaculture species Pacific White Shrimp (Litopenaeus vannamei) using vitrification and ultra-rapid laser warming - Kieran T. Smith; Kanav Khosla; Guebum Han; Tim Humphrey; Nicholas Phelps; John Bischof (Cryobiology, 2024)

Performance improvement and application of copper-based nanomaterials in membrane technology for water treatment: A review - Shuli Liu; Haoyi Guo; Zhihui Kong; Xiaohong Han; Yatong Gao; Yuhong Zhang; Glen T. Daigger; Peng Zhang; Jia Kang; Shuchun Yu; Guoting Li; Gangfu Song (Journal of Environmental Management, 2024)

INSPIRED: Inelastic neutron scattering prediction for instantaneous results and experimental design - Bowen Han; Andrei T. Savici; Mingda Li; Yongqiang Cheng (Computer Physics Communications, 2024)

Uncovering mediational pathways behind racial and socioeconomic disparities in brain volumes: insights from the UK Biobank study - May A. Beydoun; Hind A. Beydoun; Marie T. Fanelli-Kuczmarski; Yi-Han Hu; Danielle Shaked; Jordan Weiss; Shari R. Waldstein; Lenore J. Launer; Michele K. Evans; Alan B. Zonderman (GeroScience, 2024)
Mediation pathways explaining racial/ethnic and socioeconomic (SES) disparities in structural MRI markers of brain health remain underexplored. We examined racial/ethnic and SES disparities in sMRI markers and tested total, direct, and indirect effects through lifestyle, health-related, and cognition factors using a structural equations modeling approach among 36,184 UK Biobank participants aged 40–70 years at baseline assessment (47% men). Race (non-White vs. White) and lower SES-predicted poorer brain sMRI volumetric outcomes at follow-up, with racial/ethnic disparities in sMRI outcomes involving multiple pathways and SES playing a central role in those pathways. Mediational patterns differed across outcomes, with the SES-sMRI total effect being partially mediated for all outcomes. Over 20% of the total effect (TE) of race/ethnicity on WMH was explained by the indirect effect (IE), by a combination of different pathways going through SES, lifestyle, health-related, and cognition factors. This is in contrast to < 10% for total brain, gray matter (GM), white matter (WM), and frontal GM left/right. Another significant finding is that around 57% of the total effect for SES and the normalized white matter hyperintensity (WMH) was attributed to an indirect effect. This effect encompasses many pathways that involve lifestyle, health-related, and cognitive aspects. Aside from WMH, the percent of TE of SES mediated through various pathways ranged from ~ 5% for WM to > 15% up to 36% for most of the remaining sMRI outcomes, which are composed mainly of GM phenotypes. Race and SES were important determinants of brain volumetric outcomes, with partial mediation of racial/ethnic disparities through SES, lifestyle, health-related, and cognition factors.

Feasibility and mechanism of adsorption and bioreduction of hexavalent chromium using Rhodopseudomonas palustris immobilized on multiple materials - Shuli Liu; Yuhong Zhang; Yacong Duan; Xiangyu Shen; Haoyi Guo; Zhihui Kong; Yatong Gao; Xiaohong Han; Wenxiao Wang; Glen T. Daigger; Guangming Zhang; Ruihua Li; et al. (Chemosphere, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Effect of solid-state fermentation on the functionality, digestibility, and volatile profiles of pulse protein isolates - Andrea K. Stone; Dai Shi; Enyu Liu; Zahra Jafarian; Caishuang Xu; Aarti Bhagwat; Yuping Lu; Leonid Akhov; Jessica Gerein; Xiumei Han; L. Irina Zaharia; Nandhakishore Rajagopalan; et al. (Food Bioscience, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Tachol1 QTL on mouse chromosome 1 is responsible for hypercholesterolemia and diet-induced obesity - Jung Han Kim; Marvin A. Simpkins; Nicholas T. Williams; Emma Cimino; Jadyn Simon; Tanner R. Richmond; Jared Youther; Hannah Slutz; James Denvir (Mammalian Genome, 2024)

High-performance hydrophobic aerogel based on nanocellulose, graphene oxide, polyvinyl alcohol, and hexadecyltrimethoxysilane: Structure, properties, and applicability - Vy T. Nguyen; Ngoc Anh T. Pham; Truc Han T. Duong; Tan Vinh Nguyen; Lam H. Pham; Phuong H. Ly; Dang Mao Nguyen; Nguyen Thuy Ngoc Thuy; DongQuy Hoang (Journal of Environmental Chemical Engineering, 2024)

High-Resolution Melting (HRM) analysis of DNA methylation using semiconductor chip-based digital PCR - Jinuk Jeong; Yongsu Yang; Min-Sik Song; Hee-Young Won; Andrew T. Han; Songmi Kim (Genes & Genomics, 2024)

Lessons learned from a UAV survey and methane emissions calculation at a UK landfill - Han Yong; Grant Allen; Jamie Mcquilkin; Hugo Ricketts; Jacob T Shaw (Waste Management, 2024)

Predictability of monthly streamflow by considering complexity measures - Dragutin T. Mihailović; Slavica Malinović-Milićević; Francisco Javier Frau; Vijay P. Singh; Jeongwoo Han (Journal of Hydrology, 2024)

Evaluating the future total water storage change and hydrological drought under climate change over lake basins, East Africa - Ayalkibet M. Seka; Huadong Guo; Jiahua Zhang; Jiaqi Han; Eyale Bayable; Gebiaw T. Ayele; Habtamu T. Workneh; Olfa T. Bayouli; Fabien Muhirwa; Kidane W. Reda (Journal of Cleaner Production, 2024)

Clinical Investigation of Large Volume Subcutaneous Delivery up to 25 mL for Lean and Non-Lean Subjects - Xiangnan Dang; Han Shih; Rakesh Sharma; Daneen T. Angwin-Kaerner; Kathleen Lin; Shiven Kapur; Nagarajan R. Thyagarajapuram; Galen H. Shi; David S. Collins (Pharmaceutical Research, 2024)

Dry-season length affects the annual ecosystem carbon balance of a temperate semi-arid shrubland - Yanmei Mu; Xin Jia; Ziqi Ye; Tianshan Zha; Xulin Guo; T. Andrew Black; Yuqing Zhang; Shaorong Hao; Cong Han; Shengjie Gao; Shugao Qin; Peng Liu; et al. (Science of The Total Environment, 2024)

The impact of marital status on tumor aggressiveness, treatment, and screening among black and white men diagnosed with prostate cancer - Saira Khan; Lindsay Fuzzell; Marvin Langston; Yunan Han; Justin X. Moore; Keon Gilbert; Siobhan Sutcliffe; Jeannette T. Bensen; James L. Mohler; Elizabeth T.H. Fontham; Lixin Song; Marquita W. Lewis-Thames (Cancer Causes & Control, 2024)

Genomic data reveal shift in geographic source of an illegally traded songbird - Meng Yue Wu; Han Wei Chong; Yen Yi Tan; Bryan T. M. Lim; Anna M.S. Wong; Rachel Rui Ying Oh; Jessica G.H. Lee; Elize Y.X. Ng; Frank E. Rheindt (Conservation Genetics, 2024)

Examining inequities in species loss due to land use in China from an interregional trade perspective - Han Zhao; T. Reed Miller; Naoko Ishii; Akiyuki Kawasaki (Journal of Environmental Management, 2024)

Fluorescence lifetime imaging microscopy as a tool to characterize spice powder variations for quality and authenticity purposes: A ginger case study - Qing Han; Sara W. Erasmus; Arjen Bader; Christos Fryganas; Christopher T. Elliott; Saskia M. van Ruth (Food Research International, 2024)

Comparison of PM2.5 components and secondary formation during the heavily polluted period of two megacities in China - Z. Ran; X. Wang; X. Yin; Y. Liu; M. Han; Y. Cheng; J. Han; T. Jin (International Journal of Environmental Science and Technology, 2024)

Multivariate investigation of aging in mouse models expressing the Alzheimer’s protective APOE2 allele: integrating cognitive metrics, brain imaging, and blood transcriptomics - Hae Sol Moon; Ali Mahzarnia; Jacques Stout; Robert J. Anderson; Madison Strain; Jessica T. Tremblay; Zay Yar Han; Andrei Niculescu; Anna MacFarlane; Jasmine King; Allison Ashley-Koch; Darin Clark; et al. (Brain Structure and Function, 2023)

Numerical modeling of plunging jets of brine: Mass transport and implications for desalination plant outfalls - Matthew T. Flavin; Jenifer Fernandes; Rawan AlQabandi; Eric Adams; Jongyoon Han; Bader Al-Anzi (Desalination, 2023)

Phytotoxicity induced by soil-applied hydrothermally-carbonised waste amendments: effect of reaction temperature, feedstock and soil nutrition - Henry Luutu; Michael T. Rose; Shane McIntosh; Lukas Van Zwieten; Han H. Weng; Matt Pocock; Terry J. Rose (Plant and Soil, 2023)

An adoption spectrum for sustainable agriculture practices: A new framework applied to cover crop adoption - Guang Han; Meredith T. Niles (Agricultural Systems, 2023)

Potential natural attenuation of petroleum hydrocarbons in fuel contaminated soils: Focusing on anaerobic fuel biodegradation involving microbial Fe(III) reduction - Myeong-Jung Kang; Han-Suk Kim; Yidan Zhang; Kanghyun Park; Ho Young Jo; Kevin T. Finneran; Man Jae Kwon (Chemosphere, 2023)

Localized conditional induction of brain arteriovenous malformations in a mouse model of hereditary hemorrhagic telangiectasia - Lea Scherschinski; Chul Han; Yong Hwan Kim; Ethan A. Winkler; Joshua S. Catapano; Tyler D. Schriber; Peter Vajkoczy; Michael T. Lawton; S. Paul Oh (Angiogenesis, 2023)
Background Longitudinal mouse models of brain arteriovenous malformations (AVMs) are crucial for developing novel therapeutics and pathobiological mechanism discovery underlying brain AVM progression and rupture. The sustainability of existing mouse models is limited by ubiquitous Cre activation, which is associated with lethal hemorrhages resulting from AVM formation in visceral organs. To overcome this condition, we developed a novel experimental mouse model of hereditary hemorrhagic telangiectasia (HHT) with CreER-mediated specific, localized induction of brain AVMs. Methods Hydroxytamoxifen (4-OHT) was stereotactically delivered into the striatum, parietal cortex, or cerebellum of R26 CreER ; Alk1 2f/2f ( Alk1 -iKO) littermates. Mice were evaluated for vascular malformations with latex dye perfusion and 3D time-of-flight magnetic resonance angiography (MRA). Immunofluorescence and Prussian blue staining were performed for vascular lesion characterization. Results Our model produced two types of brain vascular malformations, including nidal AVMs (88%, 38/43) and arteriovenous fistulas (12%, 5/43), with an overall frequency of 73% (43/59). By performing stereotaxic injection of 4-OHT targeting different brain regions, Alk1 -iKO mice developed vascular malformations in the striatum (73%, 22/30), in the parietal cortex (76%, 13/17), and in the cerebellum (67%, 8/12). Identical application of the stereotaxic injection protocol in reporter mice confirmed localized Cre activity near the injection site. The 4-week mortality was 3% (2/61). Seven mice were studied longitudinally for a mean (SD; range) duration of 7.2 (3; 2.3−9.5) months and demonstrated nidal stability on sequential MRA. The brain AVMs displayed microhemorrhages and diffuse immune cell invasion. Conclusions We present the first HHT mouse model of brain AVMs that produces localized AVMs in the brain. The mouse lesions closely resemble the human lesions for complex nidal angioarchitecture, arteriovenous shunts, microhemorrhages, and inflammation. The model’s longitudinal robustness is a powerful discovery resource to advance our pathomechanistic understanding of brain AVMs and identify novel therapeutic targets.

Energy-efficient electrochemical recovery of gold enabled by a thiourea-based electrolyte system - Jieun Son; Jong-In Han; Yeongran Hong; Cafer T. Yavuz (Journal of Environmental Chemical Engineering, 2023)

Petrogenesis and tectonic implications of the early Paleozoic granites in the Lincang granitic batholith, southwestern China: Constraints from geochronology, geochemistry and Hf isotopes - Qian R. Xiao; Qiang Wang; Zhong Y. Liu; Fu H. Xiong; Lei Fan; Han Zhao; Ting T. Gong (Ore and Energy Resource Geology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Optimal energy harvesting efficiency from vortex-induced vibration of a circular cylinder - Peng Han; Qiaogao Huang; Guang Pan; Denghui Qin; Wei Wang; Rodolfo T. Gonçalves; Jisheng Zhao (Ocean Engineering, 2023)

Intakes of Unprocessed and Minimally Processed and Ultraprocessed Food Are Associated with Diet Quality in Female and Male Health Professionals in the United States: A Prospective Analysis - Sinara Laurini Rossato; Neha Khandpur; Chun-Han Lo; Stela Maris Jezus Castro; Jean Philippe Drouin-Chartier; Laura Sampson; Changzheng Yuan; Cristiane Murta-Nascimento; Maria Antonieta Carvalhaes; Carlos Augusto Monteiro; Qi Sun; Teresa T. Fung; et al. (Journal of the Academy of Nutrition and Dietetics, 2023)

Interpreting the variation in particle size of ground spice by high-resolution visual and spectral imaging: A ginger case study - Qing Han; Joseph Peller; Sara W. Erasmus; Christopher T. Elliott; Saskia M. van Ruth (Food Research International, 2023)

Dermal repeated dose toxicity study of the anti-breast cancer drug Formestane cream in Bama minipig - Shiyao Huang; Ziming Wu; Youyou Chen; Han Li; Linglin Zou; Alexander T. Teichmann; Yao Luo; Lifeng Zhang; Lanyang Gao (Food and Chemical Toxicology, 2023)

Complexity and chaotic behavior of the U.S. Rivers and estimation of their prediction horizon - Dragutin T. Mihailović; Slavica Malinović-Milićević; Jeongwoo Han; Vijay P. Singh (Journal of Hydrology, 2023)

Lead change of a HIF-2α antagonist guided by multiparameter optimization and utilization of an Olp→π*Ar interaction - Paul M. Wehn; Song Yang; Jonas A. Grina; James P. Rizzi; Stephen T. Schlachter; Bin Wang; Rui Xu; Hanbiao Yang; Xinlin Du; Guangzhou Han; Keshi Wang; Robert M. Czerwinski; et al. (Medicinal Chemistry Research, 2023)

Hydrothermal characteristics of the Mienhua submarine volcano in the southernmost Okinawa trough - Tzu-Ting Chen; Ho-Han Hsu; Chih-Chieh Su; Char-Shine Liu; Yunshuen Wang; Song-Chuen Chen; Emmy T. Y. Chang; Feng-Hsin Hsu; Liang-Fu Lin; Jih-Hsin Chang; Jyun-Nai Wu; Ta-Wei Hsu; et al. (Marine Geophysical Research, 2023)

Local-scale soil nematode diversity in a subtropical forest depends on the phylogenetic and functional diversity of neighbor trees - Yingbin Li; Xiaofang Du; Xiaolin Su; Xu Han; Wenju Liang; Zhengwen Wang; Helge Bruelheide; T. Martijn Bezemer; Qi Li (Plant and Soil, 2023)

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Transfer learning in a biomaterial fibrosis model identifies in vivo senescence heterogeneity and contributions to vascularization and matrix production across species and diverse pathologies - Christopher Cherry; James I. Andorko; Kavita Krishnan; Joscelyn C. Mejías; Helen Hieu Nguyen; Katlin B. Stivers; Elise F. Gray-Gaillard; Anna Ruta; Jin Han; Naomi Hamada; Masakazu Hamada; Ines Sturmlechner; et al. (GeroScience, 2023)

Comparing “apples” and “oranges” in the Woodford Shale: Pitfalls of the thermal maturity gradient approach for constraining evolution of mudrock porosity - Elizabeth T. Baruch; Stefan C. Löhr; Shujun Han; David N. Dewhurst; Alan S. Collins (Marine and Petroleum Geology, 2023)

Molecular Analysis and Sex-specific Response of the Hepcidin Gene in Yellow Perch (Perca Flavescens) Following Lipopolysaccharide Challenge - Xing Lu; Yueh-Chiang Han; Brian S. Shepherd; Ying Xiang; Dong-Fang Deng; Bryan T. Vinyard (Probiotics and Antimicrobial Proteins, 2023)

Genome-Wide Transcriptome Analysis of Rice Transporters and Its Application to Elucidate the Uncharacterized Functions of OsABCC7 Gene Using the CRISPR/Cas9 System - Van N. T. Nguyen; Yo-Han Yoo; Eok-Keun Ahn; Jong-Cheol Ko; Sunny Ahmar; Ki-Hong Jung (Journal of Plant Biology, 2023)

Abundant cilantro derived high surface area activated carbon (AC) for superior adsorption performances of cationic/anionic dyes and supercapacitor application - Shrinath Bhat; U.T. Uthappa; T. Sadhasivam; Tariq Altalhi; Sung Soo Han; Mahaveer D. Kurkuri (Chemical Engineering Journal, 2023)

Proper Orthogonal Decomposition Analysis Reveals Cell Migration Directionality During Wound Healing - Suyue Han; Duy T. Nguyen; Yahya Modarres-Sadeghi; Juan Miguel Jiménez (Annals of Biomedical Engineering, 2022)

What can occupancy models gain from time‐to‐detection data? - Dinusha Priyadarshani; Res Altwegg; Alan T. K. Lee; Wen‐Han Hwang (Ecology, 2022)
The time taken to detect a species during site occupancy surveys contains information about the observation process. Accounting for the observation process leads to better inference about site occupancy. We explore the gain in efficiency that can be obtained from time‐to‐detection (TTD) data and show that this model type has a significant benefit for estimating the parameters related to detection intensity. However, for estimating occupancy probability parameters, the efficiency improvement is generally very minor. To explore whether TTD data could add valuable information when detection intensities vary between sites and surveys, we developed a mixed exponential TTD occupancy model. This new model can simultaneously estimate the detection intensity and aggregation parameters when the number of detectable individuals at the site follows a negative binomial distribution. We found that this model provided a much better description of the occupancy patterns than conventional detection/nondetection methods among 63 bird species data from the Karoo region of South Africa. Ignoring the heterogeneity of detection intensity in the TTD model generally yielded a negative bias in the estimated occupancy probability. Using simulations, we briefly explore study design trade offs between numbers of sites and surveys for different occupancy modeling strategies.

Gene Expression Analysis of Laser-Captured Purkinje Cells in the Essential Tremor Cerebellum - Regina T. Martuscello; Karthigayini Sivaprakasam; Whitney Hartstone; Sheng-Han Kuo; Genevieve Konopka; Elan D. Louis; Phyllis L. Faust (The Cerebellum, 2022)

Tectonic controls on geomorphological dynamics and sediment dispersal in source-to-sink systems in the Qingdong Sag, Bohai Bay Basin - Z. Han; S. Dai; H. Jia; T. Liu; Z. Jiang (Australian Journal of Earth Sciences, 2022)

Sustained-release ketamine-loaded lipid-particulate system: in vivo assessment in mice - Weizhi Xu; Faheem Maqbool; Vinod Kumar; James R. Falconer; Cedric S. Cui; Trent M. Woodruff; Karin Borges; Andrew K. Whittaker; Maree T. Smith; Felicity Y. Han (Drug Delivery and Translational Research, 2022)

Rapid changes in coastal ocean microbiomes uncoupled with shifts in environmental variables - Jessica L. Gronniger; Zhao Wang; Genevieve R. Brandt; Christopher S. Ward; Despina Tsementzi; Han Mu; Junyao Gu; Zackary I. Johnson; Konstantinos T. Konstantinidis; Dana E. Hunt (Environmental Microbiology, 2022)
Summary Disturbances, here defined as events that directly alter microbial community composition, are commonly studied in host‐associated and engineered systems. In spite of global change both altering environmental averages and increasing extreme events, there has been relatively little research into the causes, persistence and population‐level impacts of disturbance in the dynamic coastal ocean. Here, we utilize 3 years of observations from a coastal time series to identify disturbances based on the largest week‐over‐week changes in the microbiome (i.e. identifying disturbance as events that alter the community composition). In general, these microbiome disturbances were not clearly linked to specific environmental factors and responsive taxa largely differed, aside from SAR11, which generally declined. However, several disturbance metagenomes identified increased phage‐associated genes, suggesting that unexplained community shifts might be caused by increased mortality. Furthermore, a category 1 hurricane, the only event that would likely be classified a priori as an environmental disturbance, was not an outlier in microbiome composition, but did enhance a bloom in seasonally abundant phytoplankton. Thus, as extreme environmental changes intensify, assumptions of what constitutes a disturbance should be re‐examined in the context of ecological history and microbiome responses.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

FDA Approaches in Monitoring Drug Quality, Forces Impacting the Drug Quality, and Recent Alternative Strategies to Assess Quality in the US Drug Supply - Philip J. Almeter; James T. Isaacs; Aaron N. Hunter; Bradley S. Henderson; Thomas Platt; Billie J. Mitchell; David Do; Alyssa B. Brainard; Joshua E. Brown; Rachael M. Stone; Bao-Han Nguyen; Matthew F. Warren; et al. (Journal of Pharmaceutical Innovation, 2022)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Trametes suaveolens-derived biochar loaded on nanoscale zero-valent iron particles for the adsorption and reduction of Cr(VI) - W.-D. Wang; H.-T. Ma; W. Lin; P. Sun; L.-K. Zhang; J.-H. Han (International Journal of Environmental Science and Technology, 2022)

Microfossil analysis of dental calculus and isotopic measurements reveal the complexity of human-plant dietary relationships in Late Bronze Age Yunnan - Tingting Wang; Dong Wei; Zhilong Jiang; Xiumin Xia; Yan Wu; Zhen Han; Yating Qu; Yaowu Hu; Benjamin T. Fuller (Archaeological and Anthropological Sciences, 2022)

A hypotonic gel-forming eye drop provides enhanced intraocular delivery of a kinase inhibitor with melanin-binding properties for sustained protection of retinal ganglion cells - Yoo Chun Kim; Henry T. Hsueh; Matthew D. Shin; Cynthia A. Berlinicke; Hyounkoo Han; Nicole M. Anders; Avelina Hemingway; Kirby T. Leo; Renee Ti Chou; HyeYoung Kwon; Matthew B. Appell; Usha Rai; et al. (Drug Delivery and Translational Research, 2022)

Sustained release ketamine-loaded porous silicon-PLGA microparticles prepared by an optimized supercritical CO2 process - Weizhi Xu; Zonglan Zhao; James Falconer; Andrew K. Whittaker; Amirali Popat; Maree T. Smith; Tushar Kumeria; Felicity Y. Han (Drug Delivery and Translational Research, 2022)

Factors Affecting Operational Cost and Productivity of Ground-Based Timber Harvesting Machines: a Meta-analysis - Libin T. Louis; Anil Raj Kizha; Adam Daigneault; Han-Sup Han; Aaron Weiskittel (Current Forestry Reports, 2022)

CRISPR Cas9- and Cas12a-mediated gusA editing in transgenic blueberry - Xiaoyan Han; Yingzhen Yang; Xue Han; John T. Ryner; Emadeldin A. H. Ahmed; Yiping Qi; Gan-yuan Zhong; Guo-qing Song (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Essential Tremor versus “ET-plus”: A Detailed Postmortem Study of Cerebellar Pathology - John T. Gionco; Whitney G. Hartstone; Regina T. Martuscello; Sheng-Han Kuo; Phyllis L. Faust; Elan D. Louis (The Cerebellum, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Utilizing MIKC-type MADS-box protein SOC1 for yield potential enhancement in maize - Guo-qing Song; Xue Han; John T. Ryner; Addie Thompson; Kan Wang (Plant Cell Reports, 2021)
Key message Overexpression of Zea mays SOC gene promotes flowering, reduces plant height, and leads to no reduction in grain production per plant, suggesting enhanced yield potential, at least, through increasing planting density. Abstract MIKC-type MADS-box gene SUPPRESSOR OF OVEREXPRESSION OF CONSTANS 1 ( SOC1 ) is an integrator conserved in the plant flowering pathway. In this study, the maize SOC1 ( ZmSOC1 ) gene was cloned and overexpressed in transgenic maize Hi-II genotype. The T 0 plants were backcrossed with nontransgenic inbred B73 to produce first generation backcross (BC 1 ) seeds. Phenotyping of both transgenic and null segregant (NT) BC 1 plants was conducted in three independent experiments. The BC 1 transgenic plants showed new attributes such as increased vegetative growth, accelerated flowering time, reduced overall plant height, and increased grain weight. Second generation backcross (BC 2 ) plants were evaluated in the field using two planting densities. Compared to BC 2 NT plants, BC 2 transgenic plants, were 12–18% shorter, flowered 5 days earlier, and showed no reduction in grain production per plant and an increase in fat, starch, and simple sugars in the grain. Transcriptome comparison in young leaves of 56-day-old BC 1 plants revealed that the overexpressed ZmSOC1 resulted in 107 differentially expressed genes. The upregulated transcription factor DNA BINDING WITH ONE FINGER 5.4 (DOF5.4) was among the genes responsible for the reduced plant height. Modulating expression of SOC1 opens a new and effective approach to promote flowering and reduce plant height, which may have potential to enhance crop yield and improve grain quality.

Use of Moringa oleifera seeds powder as bio-coagulants for the surface water treatment - H. T. Nhut; N. T. Q. Hung; B. Q. Lap; L. T. N. Han; T. Q. Tri; N. H. K. Bang; N. T. Hiep; N. M. Ky (International Journal of Environmental Science and Technology, 2021)

Self-reported experiences of discrimination in older black adults are associated with insula functional connectivity - S. Duke Han; Melissa Lamar; Debra Fleischman; Namhee Kim; David A. Bennett; Tené T. Lewis; Konstantinos Arfanakis; Lisa L. Barnes (Brain Imaging and Behavior, 2021)

Genetic diversity and population genetic structure in native Ethiopian donkeys (Equus asinus) inferred from equine microsatellite markers - E. Kefena; S. Rosenbom; A. Beja-Pereira; M. Yusuf Kurtu; J. L. Han; T. Dessie (Tropical Animal Health and Production, 2021)

Drought tolerance in selected aerobic and upland rice varieties is driven by different metabolic and antioxidative responses - Giovanni Melandri; Hamada AbdElgawad; Kristýna Floková; Diaan C. Jamar; Han Asard; Gerrit T. S. Beemster; Carolien Ruyter-Spira; Harro J. Bouwmeester (Planta, 2021)
Main conclusions Sugar-mediated osmotic acclimation and a strong antioxidative response reduce drought-induced biomass loss at the vegetative stage in rice. Abstract A clear understanding of the physiological and biochemical adaptations to water limitation in upland and aerobic rice can help to identify the mechanisms underlying their tolerance to low water availability. In this study, three indica rice varieties-IR64 (lowland), Apo (aerobic), and UPL Ri-7 (upland)-, that are characterized by contrasting levels of drought tolerance, were exposed to drought at the vegetative stage. Drought-induced changes in biomass, leaf metabolites and oxidative stress markers/enzyme activities were analyzed in each variety at multiple time points. The two drought-tolerant varieties, Apo and UPL Ri-7 displayed a reduced water use in contrast to the susceptible variety IR64 that displayed high water consumption and consequent strong leaf dehydration upon drought treatment. A sugar-mediated osmotic acclimation in UPL Ri-7 and a strong antioxidative response in Apo were both effective in limiting the drought-induced biomass loss in these two varieties, while biomass loss was high in IR64, also after recovery. A qualitative comparison of these results with the ones of a similar experiment conducted in the field at the reproductive stage showed that only Apo, which also in this stage showed the highest antioxidant power, was able to maintain a stable grain yield under stress. Our results show that different metabolic and antioxidant adaptations confer drought tolerance to aerobic and upland rice varieties in the vegetative stage. The effectiveness of these adaptations differs between developmental stages. Unraveling the genetic control of these mechanisms might be exploited in breeding for new rice varieties adapted to water-limited environments.

Kelp aquaculture in China: a retrospective and future prospects - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
Globally, China has the largest scale of kelp cultivation and production operations. However, its kelp aquaculture industry is suffering from declining germplasm diversity, degradation of agronomic traits, the presence of polluted environments, changing ocean conditions and increasing anthropological interference. This review covers two of the most commercially important kelp species in China, viz. Saccharina japonica and Undaria pinnatifida . It summarizes the history of their cultivation, production, economic and ecological benefits, their breeding programmes (e.g. inter‐ and intra‐specific hybridization and marker‐assisted selection) and efforts towards population genetic diversity and conservation. The article focuses on three significant challenges, for example genetic cross‐contamination between the wild and farmed kelp populations, ocean warming and ocean acidification. Accordingly, we outline the steps required to provide several intervention measures, for example (i) collection and preservation of wild and cultivated kelp germplasm; (ii) selection of suitable cultivation sites under changing environmental conditions; (iii) developing stress‐resistant cultivars; and finally, (iv) adoption of innovative cultivation models. The review concludes with genome‐based, designs for molecular breeding and calls for the establishment of an East Asian Kelp Consortium (EAKC). Collectively, the Chinese kelp industry could provide beneficial goods and services, for example bioenergy to fine chemicals and environmental benefits, such as carbon capture, pH amelioration and provision of habitat for many other marine species of commercial value. The strategies proposed in this article thus have the potential to not only improve but also reinvigorate the kelp industry in China and nearby Japan and Korea, in the context of both environmental health and economic benefits.

Cover Image - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
The cover image is based on the Review Article Kelp aquaculture in China: A retrospective and future prospects by Zi‐Min Hu et al., https://doi.org/10.1111/raq.12524 . image

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

NABat: A top-down, bottom-up solution to collaborative continental-scale monitoring - Brian E. Reichert; Mylea Bayless; Tina L. Cheng; Jeremy T. H. Coleman; Charles M. Francis; Winifred F. Frick; Benjamin S. Gotthold; Kathryn M. Irvine; Cori Lausen; Han Li; Susan C. Loeb; Jonathan D. Reichard; et al. (Ambio, 2021)
Collaborative monitoring over broad scales and levels of ecological organization can inform conservation efforts necessary to address the contemporary biodiversity crisis. An important challenge to collaborative monitoring is motivating local engagement with enough buy-in from stakeholders while providing adequate top-down direction for scientific rigor, quality control, and coordination. Collaborative monitoring must reconcile this inherent tension between top-down control and bottom-up engagement. Highly mobile and cryptic taxa, such as bats, present a particularly acute challenge. Given their scale of movement, complex life histories, and rapidly expanding threats, understanding population trends of bats requires coordinated broad-scale collaborative monitoring. The North American Bat Monitoring Program (NABat) reconciles top-down, bottom-up tension with a hierarchical master sample survey design, integrated data analysis, dynamic data curation, regional monitoring hubs, and knowledge delivery through web-based infrastructure. NABat supports collaborative monitoring across spatial and organizational scales and the full annual lifecycle of bats.

On-site rainwater harvesting and treatment for drinking water supply: assessment of cost and technical issues - Son H. Tran; Huyen T.T. Dang; Dung A. Dao; Viet-Anh Nguyen; Lien T. Nguyen; Viet-Anh Nguyen; Mooyoung Han (Environmental Science and Pollution Research, 2021)

Understanding patterns of distribution shifts and range expansion/contraction for small yellow croaker ( Larimichthys polyactis ) in the Yellow Sea - Qingpeng Han; Arnaud Grüss; Xiujuan Shan; Xianshi Jin; James T. Thorson (Fisheries Oceanography, 2021)
Detecting and analyzing patterns of distribution shifts and range expansion/contraction is important to understand population dynamics and changes in stock status. Here, we develop a spatio‐temporal model for yellow croaker ( Larimichthys polyactis ), which was fitted to bottom trawl survey biomass data collected in the Yellow Sea in the winter of 2001–2017. The model accounts for both spatial and spatio‐temporal structure and can potentially include the effects of surface temperature and of an annual index, the Pacific Decadal Oscillation, represented using a recently developed spatially varying coefficient model. We selected a spatio‐temporal model with no covariates based on Akaike's information criterion. The center of gravity for yellow croaker was found to move northwest between 2001 and 2010, and then southwest over the period 2010–2017. These results reflected the predicted progressive disappearance of yellow croaker density hotspots (i.e., highest density areas) in the north and southeast areas of the Yellow Sea, which resulted in the central area of the Yellow Sea becoming the only yellow croaker density hotspot in 2017. This finding has important implications for fisheries management in the context of the China–South Korea fisheries agreement, as it indicates a measurable displacement of yellow croaker biomass toward China. The exclusion of covariates from the spatio‐temporal model was not expected a priori and may be due to the facts that environmental variations are not pronounced in winter in the Yellow Sea and that the representation of spatial and spatio‐temporal structure in spatio‐temporal models accounts for a large proportion of the variability in the data.

Dissociable dopaminergic and pavlovian influences in goal-trackers and sign-trackers on a model of compulsive checking in OCD - D. M. Eagle; C. Schepisi; S. Chugh; S. Desai; S. Y. S. Han; T. Huang; J. J. Lee; C. Sobala; W. Ye; A. L. Milton; T. W. Robbins (Psychopharmacology, 2020)
Rationale Checking is a functional behaviour that provides information to guide behaviour. However, in obsessive-compulsive disorder (OCD), checking may escalate to dysfunctional levels. The processes underpinning the transition from functional to dysfunctional checking are unclear but may be associated with individual differences that support the development of maladaptive behaviour. We examined one such predisposition, sign-tracking to a pavlovian conditioned stimulus, which we previously found associated with dysfunctional checking. How sign-tracking interacts with another treatment with emerging translational validity for OCD-like checking, chronic administration of the dopamine D 2 receptor agonist quinpirole, is unknown. Objectives We tested how functional and dysfunctional checking in the rat observing response task (ORT) was affected by chronic quinpirole administration in non-autoshaped controls and autoshaped animals classified as sign-trackers or goal-trackers. Methods Sign-trackers or goal-trackers were trained on the ORT before the effects of chronic quinpirole administration on checking were assessed. Subsequently, the effects on checking of different behavioural challenges, including reward omission and the use of unpredictable reinforcement schedules, were tested. Results Prior autoshaping increased checking. Sign-trackers and goal-trackers responded differently to quinpirole sensitization, reward omission and reinforcement uncertainty. Sign-trackers showed greater elevations in dysfunctional checking, particularly during uncertainty. By contrast, goal-trackers predominantly increased functional checking responses, possibly in response to reduced discrimination accuracy in the absence of cues signalling which lever was currently active. Conclusions The results are discussed in terms of how pavlovian associations influence behaviour that becomes compulsive in OCD and how this may be dependent on striatal dopamine D 2 receptors.

Use of Microfluidics to Fabricate Bioerodable Lipid Hybrid Nanoparticles Containing Hydromorphone or Ketamine for the Relief of Intractable Pain - Minze Zhu; Andrew K. Whittaker; Xingyu Jiang; Rupei Tang; Xuanyu Li; Weizhi Xu; Changkui Fu; Maree T Smith; Felicity Y Han (Pharmaceutical Research, 2020)

Management of the poultry red mite, Dermanyssus gallinae, using silica-based acaricides - Christian Ulrichs; Young Jong Han; Magdi T. Abdelhamid; Inga Mewis (Experimental and Applied Acarology, 2020)
Four silica-based acaricides were examined in laboratory tests for their effectiveness against poultry red mite, Dermanyssus gallinae . All acaricides resulted in 100% mite mortality. Two groups of active ingredients could be differentiated. The products Silicosec ® and Ewazid ® , based on naturally occurring diatomaceous earth (DE), killed 100% of adult D. gallinae within 48 h exposure time. The time to kill 50% of the mites (LT 50 ) was calculated to be 31.7 and 34.9 h, respectively. The other two products, containing aggregates and agglomerates of pyrogenic synthetic amorphous silicon dioxide as active ingredients, killed the mites in a significantly shorter time: LT 50 was 6.3 h for the liquid product Fossil Shield ® Instant White and 11.8 h for the powdery product Fossil Shield 90.0 White. This is more remarkable as the quantities of active ingredients used for the DE treatments were several folds higher. The effectiveness of all tested products was also shown in practical tests. A professional company treated five chicken houses on one farm in the Berlin–Brandenburg region with the test products, three houses with Fossil Shield Instant White and one each with Ewazid and Silicosec. Over a period of 46 weeks after stocking, the mite development in the houses was assessed. Only in one of the houses, treated with Fossil Shield Instant White, the mite population remained permanently low. In two houses treated with Fossil Shield Instant White, small mite colonies appeared in week 36, which were controlled by a follow-up spot treatment in week 41. In the houses treated with DE, the first mite colonies appeared 12 weeks after stocking. The number increased continuously over the experimental period and in week 31 after stocking there were clearly visible colonies (2–3 cm diameter) and the first mites could also be detected on the chicken eggs. At this time both houses were treated again with a follow-up spot-treatment, which only led to a slight improvement in one house and to a stabilization of the infestation in the other house. In week 41, large mite colonies were detected in both houses. A spot treatment at this point was ineffective in reducing the infestation. The tests showed faster acaricidal action of the products with the synthetic active ingredients compared to the natural DE-based products. This matches the shorter killing times under laboratory conditions. The experiments in a commercial chicken farm showed that it is possible to control the mite population for a period of 46 weeks by using physically effective SiO 2 -based products. These products are therefore an effective alternative to the use of chemical acaricides.

Simultaneous fluorescence imaging of distinct nerve and blood vessel patterns in dual Thy1-YFP and Flt1-DsRed transgenic mice - Samuel M. Santosa; Kai Guo; Michael Yamakawa; Evguenia Ivakhnitskaia; Neeraj Chawla; Tara Nguyen; Kyu-Yeon Han; Masatsugu Ema; Mark I. Rosenblatt; Jin-Hong Chang; Dimitri T. Azar (Angiogenesis, 2020)

Carbapenem-resistant Enterobacteriaceae in patients with bacteraemia at tertiary hospitals in South Africa, 2015 to 2018 - O. Perovic; H. Ismail; V. Quan; C. Bamford; T. Nana; V. Chibabhai; P. Bhola; P. Ramjathan; K. Swe Swe-Han; J. Wadula; A. Whitelaw; M. Smith; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Traits mediate drought effects on wood carbon fluxes - Zhenhong Hu; Han Y. H. Chen; Chao Yue; Xiao Ying Gong; Junjiong Shao; Guiyao Zhou; Jiawei Wang; Minhuang Wang; Jianyang Xia; Yongtao Li; Xuhui Zhou; Sean T. Michaletz (Global Change Biology, 2020)
CO 2 fluxes from wood decomposition represent an important source of carbon from forest ecosystems to the atmosphere, which are determined by both wood traits and climate influencing the metabolic rates of decomposers. Previous studies have quantified the effects of moisture and temperature on wood decomposition, but these effects were not separated from the potential influence of wood traits. Indeed, it is not well understood how traits and climate interact to influence wood CO 2 fluxes. Here, we examined the responses of CO 2 fluxes from dead wood with different traits (angiosperm and gymnosperm) to 0%, 35%, and 70% rainfall reduction across seasonal temperature gradients. Our results showed that drought significantly decreased wood CO 2 fluxes, but its effects varied with both taxonomical group and drought intensity. Drought‐induced reduction in wood CO 2 fluxes was larger in angiosperms than gymnosperms for the 35% rainfall reduction treatment, but there was no significant difference between these groups for the 70% reduction treatment. This is because wood nitrogen density and carbon quality were significantly higher in angiosperms than gymnosperms, yielding a higher moisture sensitivity of wood decomposition. These findings were demonstrated by a significant positive interaction effect between wood nitrogen and moisture on CO 2 fluxes in a structural equation model. Additionally, we ascertained that a constant temperature sensitivity of CO 2 fluxes was independent of wood traits and consistent with previous estimates for extracellular enzyme kinetics. Our results highlight the key role of wood traits in regulating drought responses of wood carbon fluxes. Given that both climate and forest management might extensively modify taxonomic compositions in the future, it is critical for carbon cycle models to account for such interactions between wood traits and climate in driving dynamics of wood decomposition.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Rapid Increases in Bat Activity and Diversity after Wetland Construction in an Urban Ecosystem - Kevin A. Parker; Brian T. Springall; Reuben A. Garshong; Ashley N. Malachi; Lauren E. Dorn; Alicia Costa-Terryll; Rachael A. Mathis; Alayna N. Lewis; Cassandra L. MacCheyne; Tronjay T. Davis; Alexis D. Rice; Nyla Y. Varh; et al. (Wetlands, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

A Sustained Ocean Observing System in the Indian Ocean for Climate Related Scientific Knowledge and Societal Needs - J. C. Hermes; Y. Masumoto; L. M. Beal; M. K. Roxy; J. Vialard; M. Andres; H. Annamalai; S. Behera; N. D’Adamo; T. Doi; M. Feng; W. Han; et al. (Frontiers in Marine Science, 2019)

Toxicity testing of cosmetic ingredients using gametophyte beads of the brown alga Undaria pinnatifida (Laminariales, Phaeophyta) - Hojun Lee; Juseon Lee; Murray T. Brown; Jihae Park; Christophe Vieira; Taejun Han (Journal of Applied Phycology, 2019)

Optogenetic stimulation of basal forebrain parvalbumin neurons modulates the cortical topography of auditory steady-state responses - Eunjin Hwang; Ritchie E. Brown; Bernat Kocsis; Tae Kim; James T. McKenna; James M. McNally; Hio-Been Han; Jee Hyun Choi (Brain Structure and Function, 2019)

Ocean acidification increases iodine accumulation in kelp‐based coastal food webs - Dong Xu; Georgina Brennan; Le Xu; Xiao W. Zhang; Xiao Fan; Wen T. Han; Thomas Mock; Andrew McMinn; David A. Hutchins; Naihao Ye (Global Change Biology, 2019)
Kelp are main iodine accumulators in the ocean, and their growth and photosynthesis are likely to benefit from elevated seawater CO 2 levels due to ocean acidification. However, there are currently no data on the effects of ocean acidification on iodine metabolism in kelp. As key primary producers in coastal ecosystems worldwide, any change in their iodine metabolism caused by climate change will potentially have important consequences for global geochemical cycles of iodine, including iodine levels of coastal food webs that underpin the nutrition of billions of humans around the world. Here, we found that elevated p CO 2 enhanced growth and increased iodine accumulation not only in the model kelp Saccharina japonica using both short‐term laboratory experiment and long‐term in situ mesocosms, but also in several other edible and ecologically significant seaweeds using long‐term in situ mesocosms. Transcriptomic and proteomic analysis of S. japonica revealed that most vanadium‐dependent haloperoxidase genes involved in iodine efflux during oxidative stress are down‐regulated under increasing p CO 2 , suggesting that ocean acidification alleviates oxidative stress in kelp, which might contribute to their enhanced growth. When consumed by abalone ( Haliotis discus), elevated iodine concentrations in S. japonica caused increased iodine accumulation in abalone, accompanied by reduced synthesis of thyroid hormones. Thus, our results suggest that kelp will benefit from ocean acidification by a reduction in environmental stress however; iodine levels, in kelp‐based coastal food webs will increase, with potential impacts on biogeochemical cycles of iodine in coastal ecosystems.

Detecting hydrological consistency between soil moisture and precipitation and changes of soil moisture in summer over the Tibetan Plateau - X. Meng; R. Li; L. Luan; S. Lyu; T. Zhang; Y. Ao; B. Han; L. Zhao; Y. Ma (Climate Dynamics, 2018)

Fluorescent reporter transgenic mice for in vivo live imaging of angiogenesis and lymphangiogenesis - Susan J. Doh; Michael Yamakawa; Samuel M. Santosa; Mario Montana; Kai Guo; Joseph R. Sauer; Nicholas Curran; Kyu-Yeon Han; Charles Yu; Masatsugu Ema; Mark I. Rosenblatt; Jin-Hong Chang; et al. (Angiogenesis, 2018)

A hybrid proline-rich cell-wall protein gene JsPRP1 from Juglans sigillata Dode confers both biotic and abiotic stresses in transgenic tobacco plants - D. Q. Liu; Q. Han; T. Shah; C. Y. Chen; Q. Wang; B. F. Tang; F. Ge (Trees, 2018)

Remote sensing study of wetlands in the Pearl River Delta during 1995–2015 with the support vector machine method - Xiaosong Han; Jiayi Pan; Adam T. Devlin (Frontiers of Earth Science, 2018)

Winter hatching in New England populations of invasive pheretimoid earthworms Amynthas agrestis and Amynthas tokioensis: a limit on population growth, or aid in peripheral expansion? - Josef H. Görres; Samantha T. Connolly; Chih-Han Chang; Nell R. Carpenter; Erin L. Keller; Maryam Nouri-Aiin; Joseph J. Schall (Biological Invasions, 2018)

Observed and modelled temperature and precipitation extremes over Southeast Asia from 1972 to 2010 - W. K. Cheong; B. Timbal; N. Golding; S. Sirabaha; K. F. Kwan; T. A. Cinco; B. Archevarahuprok; V. H. Vo; D. Gunawan; S. Han (International Journal of Climatology, 2018)
Regional assessments of trends in climate extremes are necessary for countries to make informed decisions about adaptation strategies and to put these changes into a global context. A workshop bringing together several Southeast Asian countries has delivered a new set of daily weather observations suitable to analyse the changes in temperature and precipitation extremes between 1972 and 2010. The use of a consistent and widely tested methodology in this study allows a direct comparison with results from other parts of the world. Trends in a range of climate extremes indices were assessed focusing on spatial variation in these trends. For most locations temperature trends obtained in this study appear broadly consistent with previous assessments; for some locations stronger trends have been detected through the inclusion of new data. In contrast to earlier studies, evidence of trends in precipitation extremes is emerging, with significant increasing trends in both regional and subregional data. In addition, large correlations between regional rainfall extremes and large‐scale features such as El Niño‐Southern Oscillation and the Indian Ocean Dipole were identified. Finally, the observed trends are compared with a regional climate model reconstruction of the historical period. It was found that the model captures very well the trends and spatial variation of temperature extremes across the region, albeit with an underestimation of the more extreme indices. In contrast, the trends in precipitation extremes are largely overestimated, particularly in the western side of Southeast Asia.

Comprehensive transcriptome analyses correlated with untargeted metabolome reveal differentially expressed pathways in response to cell wall alterations - Nathan T. Reem; Han-Yi Chen; Manhoi Hur; Xuefeng Zhao; Eve Syrkin Wurtele; Xu Li; Ling Li; Olga Zabotina (Plant Molecular Biology, 2018)

Large soil organic carbon increase due to improved agronomic management in the North China Plain from 1980s to 2010s - Daorui Han; Martin Wiesmeier; Richard T. Conant; Anna Kühnel; Zhigang Sun; Ingrid Kögel‐Knabner; Ruixing Hou; Peifei Cong; Rubiao Liang; Zhu Ouyang (Global Change Biology, 2018)
Agricultural soils are widely recognized to be capable of carbon sequestration that contributes to mitigating CO 2 emissions. To better understand soil organic carbon ( SOC ) stock dynamics and its driving and controlling factors corresponding with a period of rapid agronomic evolution from the 1980s to the 2010s in the North China Plain ( NCP ), we collected data from two region‐wide soil sampling campaigns (in the 1980s and 2010s) and conducted an analysis of the controlling factors using the random forest model. Between the 1980s and 2010s, environmental (i.e. soil salinity/fertility) and societal (i.e. policy/techniques) factors both contributed to adoption of new management practices (i.e. chemical fertilizer application/mechanization). Results of our work indicate that SOC stocks in the NCP croplands increased significantly, which also closely related to soil total nitrogen changes. Samples collected near the surface (0–20 cm) and deeper (20–40 cm) both increased by an average of 9.4 and 5.1 Mg C ha −1 , respectively, which are equivalent to increases of 73% and 56% compared with initial SOC stocks in the 1980s. The annual carbon sequestration amount in surface soils reached 10.9 Tg C year −1 , which contributed an estimated 43% of total carbon sequestration in all of China's cropland on just 27% of its area. Successful desalinization and the subsequent increases in carbon (C) inputs, induced by agricultural projects and policies intended to support crop production (i.e. reconstruction of low yield farmland, and agricultural subsidies), combined with improved cultivation practices (i.e. fertilization and straw return) since the early 1980s were the main drivers for the SOC stock increase. This study suggests that rehabilitation of NCP soils to reduce salinity and increase crop yields have also served as a pathway for substantial soil C sequestration.

African origin and global distribution patterns: Evidence inferred from phylogenetic and biogeographical analyses of ectomycorrhizal fungal genus Strobilomyces - Li H. Han; Bang Feng; Gang Wu; Roy E. Halling; Bart Buyck; Nourou S. Yorou; Sydney T. N. Ebika; Zhu L. Yang (Journal of Biogeography, 2018)
Aim The ectomycorrhizal genus Strobilomyces is widely distributed throughout many parts of the world, but its origin, divergence and distribution patterns remain largely unresolved. In this study, we aim to explore the species diversity, distribution and evolutionary patterns of Strobilomyces on a global scale by establishing a general phylogenetic framework with extensive sampling. Location Africa, Australasia, East Asia, Europe, North America, Central America and Southeast Asia. Methods The genealogical concordance phylogenetic species recognition method was used to delimit phylogenetic species. Divergence times were estimated using a Bayesian uncorrelated lognormal relaxed molecular clock. The ancestral area and host of Strobilomyces were inferred via the programs rasp and mesquite . The change of diversification rate over time was estimated using Ape, Laser and Bammtools software packages. Results We recognize a novel African clade and 49 phylogenetic species with morphological evidence, including 18 new phylogenetic species and 23 previously described ones. Strobilomyces probably originated in Africa, in association with Detarioideae/Phyllanthaceae/Monotoideae during the early Eocene. The dispersal to Southeast Asia can be explained by Wolfe's “Boreotropical migration” hypothesis. East Asia, Australasia, Europe and North/Central America are primarily the recipients of immigrant taxa during the Oligocene or later. A rapid radiation implied by one diversification shift was inferred within Strobilomyces during the Miocene. Main conclusions An unexpected phylogenetic species diversity within Strobilomyces was uncovered. The highest diversity, resulting probably from a rapid radiation, was found in East Asia. Dispersal played an important role in the current distribution pattern of Strobilomyces . The Palaeotropical disjunction is explained by species dispersal from Africa to Southeast Asia through boreotropical forests during the early Eocene. Species from the Northern Hemisphere and Australasia are largely derived from immigrant ancestors from Southeast Asia.

Prox1-GFP/Flt1-DsRed transgenic mice: an animal model for simultaneous live imaging of angiogenesis and lymphangiogenesis - Wei Zhong; Xinbo Gao; Shuangyong Wang; Kyuyeon Han; Masatsugu Ema; Susanne Adams; Ralf H. Adams; Mark I. Rosenblatt; Jin-Hong Chang; Dimitri T. Azar (Angiogenesis, 2017)

Removal of Cr(VI) and phenol coupled with the reduction of sulfate by sulfate-reducing bacteria sludge - X. Han; T.-X. Zhou; S.-W. Xu; Y. Li; Y.-F. Wang; Y. Liu (International Journal of Environmental Science and Technology, 2017)

Urban CO2 emissions in Xi’an and Bangalore by commuters: implications for controlling urban transportation carbon dioxide emissions in developing countries - Yuanqing Wang; Liu Yang; Sunsheng Han; Chao Li; T. V. Ramachandra (Mitigation and Adaptation Strategies for Global Change, 2017)

Widespread generalist clones are associated with range and niche expansion in allopolyploids of Pacific Northwest Hawthorns ( Crataegus L.) - J. M. Coughlan; S. Han; S. Stefanović; T. A. Dickinson (Molecular Ecology, 2017)
Range and niche expansion are commonly associated with transitions to asexuality, polyploidy and hybridity (allopolyploidy) in plants. The ability of asexual polyploids to colonize novel habitats may be due to widespread generalist clones, multiple ecologically specialized clones, or may be a neutral by‐product of multiple, independent origins of asexual polyploids throughout the range. We have quantified niche size and divergence for hawthorns of the Pacific Northwest using data from herbarium vouchers with known cytotypes. We find that all polyploid niches diverge from that of the diploid range, and allopolyploids have the broadest niches. Allotetraploids have the largest niche and the widest geographic distribution. We then assessed the genetic mechanism of range expansion by surveying the ecological and geographic distribution of genotypes within each cytotype from sites in which fine‐scale habitat assessments were completed. We find no isolation by either geographic or ecological distance in allopolyploids, suggesting high dispersal and colonization ability. In contrast, autotriploids and diploids show patterns of isolation by geographic distance. We also compared the geographic and ecological distributions of clonal genotypes with those of randomly drawn sites of the most widespread cytotype. We found that most clones are geographically widespread and occur in a variety of habitats. We interpret these findings to suggest that patterns of range and niche expansion in Pacific Northwest Hawthorns may stem from these widespread, ecologically generalist clones of hybrid origin.

Transgenic Mice Overexpressing the Divalent Metal Transporter 1 Exhibit Iron Accumulation and Enhanced Parkin Expression in the Brain - Cheng-Wu Zhang; Yee Kit Tai; Bing-Han Chai; Katherine C. M. Chew; Eng-Tat Ang; Fai Tsang; Bryce W. Q. Tan; Eugenia T. E. Hong; Abu Bakar Ali Asad; Kai-Hsiang Chuang; Kah-Leong Lim; Tuck Wah Soong (NeuroMolecular Medicine, 2017)

Soil Organic Carbon Dynamics Responses to Soil Fertility in the Agricultural Regions of China - D. L. Han; X. P. Zhu; H. T. Jia; P. J. Yu (Agricultural Research, 2017)

Study on the application of an activator for steel slag powder–cement in muddy soil - Y. K. Wu; X. S. Hu; R. Hu; T. Han; J. L. Yu (European Journal of Environmental and Civil Engineering, 2017)

Molecular response of Sargassum vulgare to acidification at volcanic CO 2 vents: insights from de novo transcriptomic analysis - Amit Kumar; Immacolata Castellano; Francesco Paolo Patti; Massimo Delledonne; Hamada Abdelgawad; Gerrit T. S. Beemster; Han Asard; Anna Palumbo; Maria Cristina Buia (Molecular Ecology, 2017)
Ocean acidification is an emerging problem that is expected to impact ocean species to varying degrees. Currently, little is known about its effect on molecular mechanisms induced in fleshy macroalgae. To elucidate genome wide responses to acidification, a transcriptome analysis was carried out on Sargassum vulgare populations growing under acidified conditions at volcanic CO 2 vents and compared with populations in a control site. Several transcripts involved in a wide range of cellular and metabolic processes were differentially expressed. No drastic changes were observed in the carbon acquisition processes and RuBis CO level. Moreover, relatively few stress genes, including those for antioxidant enzymes and heat‐shock proteins, were affected. Instead, increased expression of transcripts involved in energy metabolism, photosynthetic processes and ion homeostasis suggested that algae increased energy production to maintain ion homeostasis and other cellular processes. Also, an increased allocation of carbon to cell wall and carbon storage was observed. A number of genes encoding proteins involved in cellular signalling, information storage and processing and transposition were differentially expressed between the two conditions. The transcriptional changes of key enzymes were largely confirmed by enzymatic activity measurements. Altogether, the changes induced by acidification indicate an adaptation of growth and development of S. vulgare at the volcanic CO 2 vents, suggesting that this fleshy alga exhibits a high plasticity to low pH and can adopt molecular strategies to grow also in future more acidified waters.

Microstructure and Ultrastructure Alterations in the Pallium of Immature Mice Exposed to Cadmium - X. F. Yang; Q. G. Han; D. Y. Liu; H. T. Zhang; G. Y. Fan; J. Y. Ma; Z. L. Wang (Biological Trace Element Research, 2016)

Detection of a New Hainan Gibbon (Nomascus hainanus) Group Using Acoustic Call Playback - Jessica V. Bryant; Aurélien Brulé; Michelle H. G. Wong; Xiaojiang Hong; Zhaoli Zhou; Wentao Han; Timothy E. Jeffree; Samuel T. Turvey (International Journal of Primatology, 2016)

The macroecology of infectious diseases: a new perspective on global‐scale drivers of pathogen distributions and impacts - Patrick R. Stephens; Sonia Altizer; Katherine F. Smith; A. Alonso Aguirre; James H. Brown; Sarah A. Budischak; James E. Byers; Tad A. Dallas; T. Jonathan Davies; John M. Drake; Vanessa O. Ezenwa; Maxwell J. Farrell; et al. (Ecology Letters, 2016)
Identifying drivers of infectious disease patterns and impacts at the broadest scales of organisation is one of the most crucial challenges for modern science, yet answers to many fundamental questions remain elusive. These include what factors commonly facilitate transmission of pathogens to novel host species, what drives variation in immune investment among host species, and more generally what drives global patterns of parasite diversity and distribution? Here we consider how the perspectives and tools of macroecology, a field that investigates patterns and processes at broad spatial, temporal and taxonomic scales, are expanding scientific understanding of global infectious disease ecology. In particular, emerging approaches are providing new insights about scaling properties across all living taxa, and new strategies for mapping pathogen biodiversity and infection risk. Ultimately, macroecology is establishing a framework to more accurately predict global patterns of infectious disease distribution and emergence.

Strong inhibition of betanodavirus replication by ribavirin targeting RNA ‐dependent RNA polymerase - Y‐C Huang; T‐S Lin; C Peng; N‐L Chan; Y‐S Han (Journal of Fish Diseases, 2016)

On the stability of colonnade structural systems under static and dynamic loading conditions - V. Sarhosis; P. Asteris; T. Wang; W. Hu; Y. Han (Bulletin of Earthquake Engineering, 2016)

Biocontrol potential of antagonist Bacillus subtilis Tpb55 against tobacco black shank - T. Han; C. You; L. Zhang; C. Feng; C. Zhang; J. Wang; F. Kong (BioControl, 2016)

Effects of light shading and climatic conditions on the metabolic behavior of flonicamid in red bell pepper - Da-I Jung; Waziha Farha; A. M. Abd El-Aty; Sung-Woo Kim; Md. Musfiqur Rahman; Jeong-Heui Choi; Md. Humayun Kabir; So Jeong Im; Young-Jun Lee; Lieu. T. B. Truong; Ho-Chul Shin; Geon-Jae Im; et al. (Environmental Monitoring and Assessment, 2016)

Toxicity tests using the kelp Undaria pinnatifida for heavy metal risk assessment - Jihae Park; Gyo-Sun Jin; Mi Sook Hwang; Murray T. Brown; Taejun Han (Toxicology and Environmental Health Sciences, 2016)

Cognition and Depression Following Deep Brain Stimulation of the Subthalamic Nucleus and Globus Pallidus Pars Internus in Parkinson’s Disease: A Meta-Analysis - Hannah L. Combs; Bradley S. Folley; David T. R. Berry; Suzanne C. Segerstrom; Dong Y. Han; Amelia J. Anderson-Mooney; Brittany D. Walls; Craig van Horne (Neuropsychology Review, 2015)

Genetic polymorphism of APOB is associated with diabetes mellitus in sickle cell disease - Xu Zhang; Wei Zhang; Santosh L. Saraf; Mehdi Nouraie; Jin Han; Michel Gowhari; Johara Hassan; Galina Miasnikova; Adelina Sergueeva; Sergei Nekhai; Rick Kittles; Roberto F. Machado; et al. (Human Genetics, 2015)

The Domain II S4-S5 Linker in Nav1.9: A Missense Mutation Enhances Activation, Impairs Fast Inactivation, and Produces Human Painful Neuropathy - Chongyang Han; Yang Yang; Bianca T. A. de Greef; Janneke G. J. Hoeijmakers; Monique M. Gerrits; Camiel Verhamme; Jian Qu; Giuseppe Lauria; Ingemar S. J. Merkies; Catharina G. Faber; Sulayman D. Dib-Hajj; Stephen G. Waxman (NeuroMolecular Medicine, 2015)

Application of a high-surface-area schwertmannite in the removal of arsenate and arsenite - J. Song; S.-Y. Jia; H.-T. Ren; S.-H. Wu; X. Han (International Journal of Environmental Science and Technology, 2015)

Response of a phytoplanktonic assemblage to copper and zinc enrichment in microcosm - Lalit K. Pandey; T. Han; J. P. Gaur (Ecotoxicology, 2015)

Contrasting responses in leaf nutrient-use strategies of two dominant grass species along a 30-yr temperate steppe grazing exclusion chronosequence - Xiao-Tao Lü; Grégoire T. Freschet; Elena Kazakou; Zheng-Wen Wang; Li-Shi Zhou; Xing-Guo Han (Plant and Soil, 2015)

Functionality and prevalence of trehalose‐based oligosaccharides as novel compatible solutes in ascospores of N eosartorya fischeri ( A spergillus fischeri ) and other fungi - Timon T. Wyatt; M. Richard van Leeuwen; Elena A. Golovina; Folkert A. Hoekstra; Eric J. Kuenstner; Edward A. Palumbo; Nicole L. Snyder; Cobus Visagie; Alex Verkennis; John E. Hallsworth; Han A.B. Wösten; Jan Dijksterhuis (Environmental Microbiology, 2015)
Summary Ascospores of N eosartorya , B yssochlamys and T alaromyces can be regarded as the most stress‐resistant eukaryotic cells. They can survive exposure at temperatures as high as 85° C for 100 min or more. N eosartorya fischeri ascospores are more viscous and more resistant to the combined stress of heat and desiccation than the ascospores of T alaromyces macrosporus which contain predominantly trehalose. These ascospores contain trehalose‐based oligosaccharides ( TOS ) that are novel compatible solutes, which are accumulated to high levels. These compounds are also found in other members of the genus N eosartorya and in some other genera within the order Eurotiales that also include B yssochlamys and T alaromyces . The presence of oligosaccharides was observed in species that had a relatively high growth temperature. TOS glasses have a higher glass transition temperature ( T g ) than trehalose, and they form a stable glass with crystallizing molecules, such as mannitol. Our data indicate that TOS are important for prolonged stabilization of cells against stress. The possible unique role of these solutes in protection against dry heat conditions is discussed.

A decrease in bulk water and mannitol and accumulation of trehalose and trehalose‐based oligosaccharides define a two‐stage maturation process towards extreme stress resistance in ascospores of N eosartorya fischeri ( A spergillus fischeri ) - Timon T. Wyatt; Elena A. Golovina; Richard van Leeuwen; John E. Hallsworth; Han A.B. Wösten; Jan Dijksterhuis (Environmental Microbiology, 2015)
Summary Fungal propagules survive stresses better than vegetative cells. N eosartorya fischeri, an A spergillus teleomorph, forms ascospores that survive high temperatures or drying followed by heat. Not much is known about maturation and development of extreme stress resistance in fungal cells. This study provides a novel two‐step model for the acquisition of extreme stress resistance and entry into dormancy. Ascospores of 11‐ and 15‐day‐old cultures exhibited heat resistance, physiological activity, accumulation of compatible solutes and a steep increase in cytoplasmic viscosity. Electron spin resonance spectroscopy indicated that this stage is associated with the removal of bulk water and an increase of chemical stability. Older ascospores from 15‐ to 50‐day‐old cultures showed no changes in compatible solute content and cytoplasmic viscosity, but did exhibit a further increase of heat resistance and redox stability with age. This stage was also characterized by changes in the composition of the mixture of compatible solutes. Mannitol levels decreased and the relative quantities of trehalose and trehalose‐based oligosaccharides increased. Dormant ascospores of N . fischeri survive in low‐water habitats. After activation of the germination process, the stress resistance decreases, compatible solutes are degraded and the cellular viscosity drops. After 5 h, the hydrated cells enter the vegetative stage and redox stability has decreased notably.

Patch or mosaic: bat activity responds to fine-scale urban heterogeneity in a medium-sized city in the United States - Han Li; Kenneth T. Wilkins (Urban Ecosystems, 2014)

Health Literacy and Pap Testing in Insured Women - K. M. Mazor; A. E. Williams; D. W. Roblin; B. Gaglio; S. L. Cutrona; M. E. Costanza; P. K. J. Han; J. L. Wagner; H. Fouayzi; T. S. Field (Journal of Cancer Education, 2014)

Impact of ubiquitous computing technologies on changing travel and land use patterns - S. H. Lee; Y. T. Leem; J. H. Han (International Journal of Environmental Science and Technology, 2014)

Mice deficient in phosphodiesterase-4A display anxiogenic-like behavior - Rolf T. Hansen; Marco Conti; Han-Ting Zhang (Psychopharmacology, 2014)

Erratum to: Rapid Determination of Mercury in Contaminated Soil and Plant Samples Using Portable Mercury Direct Analyzer Without Sample Preparation, a Comparative Study - John G. Kelly; Fengxiang X. Han; Yi Su; Yunjun Xia; Valerie Philips; Zhiqi Shi; David L. Monts; Sergio T. Pichardo; Kang Xia (Water, Air, & Soil Pollution, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Generalities in grazing and browsing ecology: using across-guild comparisons to control contingencies - Johan T. du Toit; Han Olff (Oecologia, 2014)

Keratinocyte growth factor and thiazolidinediones and linolenic acid differentiate characterized mammary fat pad adipose stem cells isolated from prepubertal Korean black goat to epithelial and adipogenic lineage - A. M. M. T Reza; S. Shiwani; N. K. Singh; J. D. Lohakare; S. J. Lee; D. K. Jeong; J. Y. Han; D. Rengaraj; B. W. Lee (In Vitro Cellular & Developmental Biology - Animal, 2014)

The value of multiple earthquake missions: the EEFIT L’Aquila Earthquake experience - T. Rossetto; D. D’Ayala; F. Gori; R. Persio; J. Han; V. Novelli; S. M. Wilkinson; D. Alexander; M. Hill; S. Stephens; S. Kontoe; G. Elia; et al. (Bulletin of Earthquake Engineering, 2014)

NtERF32: a non-NIC2 locus AP2/ERF transcription factor required in jasmonate-inducible nicotine biosynthesis in tobacco - Marta T. Sears; Hongbo Zhang; Paul J. Rushton; Martin Wu; Shengcheng Han; Anthony J. Spano; Michael P. Timko (Plant Molecular Biology, 2014)

Isolation and characterization of two VpYABBY genes from wild Chinese Vitis pseudoreticulata - J. Xiang; R. Q. Liu; T. M. Li; L. J. Han; Y. Zou; T. F. Xu; J. Y. Wei; Y. J. Wang; Y. Xu (Protoplasma, 2013)

Small- and medium-sized enterprise post-disaster reconstruction management patterns and application - Zhujun Liu; Jiuping Xu; Bernard T. Han (Natural Hazards, 2013)

Erratum to: Regulation of Phytohormone Biosynthesis and Accumulation in Arabidopsis Following Treatment with Commercial Extract from the Marine Macroalga Ascophyllum nodosum - Owen S. D. Wally; Alan T. Critchley; David Hiltz; James S. Craigie; Xiumei Han; L. Irina Zaharia; Suzanne R. Abrams; Balakrishnan Prithiviraj (Journal of Plant Growth Regulation, 2013)

Regulation of Phytohormone Biosynthesis and Accumulation in Arabidopsis Following Treatment with Commercial Extract from the Marine Macroalga Ascophyllum nodosum - Owen S. D. Wally; Alan T. Critchley; David Hiltz; James S. Craigie; Xiumei Han; L. Irina Zaharia; Suzanne R. Abrams; Balakrishnan Prithiviraj (Journal of Plant Growth Regulation, 2013)

Reconstructing the origin and dispersal patterns of village chickens across E ast A frica: insights from autosomal markers - J. M. Mwacharo; K. Nomura; H. Hanada; J. L. Han; T. Amano; O. Hanotte (Molecular Ecology, 2013)
Unravelling the genetic history of any livestock species is central to understanding the origin, development and expansion of agricultural societies and economies. Domestic village chickens are widespread in Africa. Their close association with, and reliance on, humans for long‐range dispersal makes the species an important biological marker in tracking cultural and trading contacts between human societies and civilizations across time. Archaezoological and linguistic evidence suggest a complex history of arrival and dispersion of the species on the continent, with mitochondrial DNA (mt DNA ) D‐loop analysis revealing the presence of five distinct haplogroups in East African village chickens. It supports the importance of the region in understanding the history of the species and indirectly of human interactions. Here, through a detailed analysis of 30 autosomal microsatellite markers genotyped in 657 village chickens from four East African countries (Kenya, Uganda, Ethiopia and Sudan), we identify three distinct autosomal gene pools ( I , II and III ). Gene pool I is predominantly found in Ethiopia and Sudan, while II and III occur in both Kenya and Uganda. A gradient of admixture for gene pools II and III between the Kenyan coast and Uganda's hinterland ( P = 0.001) is observed, while gene pool I is clearly separated from the other two. We propose that these three gene pools represent genetic signatures of separate events in the history of the continent that relate to the arrival and dispersal of village chickens and humans across the region. Our results provide new insights on the history of chicken husbandry which has been shaped by terrestrial and maritime contacts between ancient and modern civilizations in Asia and East Africa.

Fruit production in three masting tree species does not rely on stored carbon reserves - Günter Hoch; Rolf T. W. Siegwolf; Sonja G. Keel; Christian Körner; Qingmin Han (Oecologia, 2013)

Seagrass–Sediment Feedback: An Exploration Using a Non-recursive Structural Equation Model - Eelke O. Folmer; Matthijs van der Geest; Erik Jansen; Han Olff; T. Michael Anderson; Theunis Piersma; Jan A. van Gils (Ecosystems, 2012)

Massive invasion of Arctodiaptomus dorsalis (Copepoda, Calanoida, Diaptomidae) in Philippine lakes: a threat to Asian zooplankton biodiversity? - Rey Donne S. Papa; Huiming Li; Dino T. Tordesillas; Boping Han; Henri J. Dumont (Biological Invasions, 2012)

Specific herbivore‐induced volatiles defend plants and determine insect community composition in the field - Y. Xiao; Q. Wang; M. Erb; T. C. J. Turlings; L. Ge; L. Hu; J. Li; X. Han; T. Zhang; J. Lu; G. Zhang; Y. Lou (Ecology Letters, 2012)
In response to insect attack, plants release complex blends of volatile compounds. These volatiles serve as foraging cues for herbivores, predators and parasitoids, leading to plant‐mediated interactions within and between trophic levels. Hence, plant volatiles may be important determinants of insect community composition. To test this, we created rice lines that are impaired in the emission of two major signals, S‐ linalool and ( E )‐β‐caryophyllene. We found that inducible S‐ linalool attracted predators and parasitoids as well as chewing herbivores, but repelled the rice brown planthopper Nilaparvata lugens , a major pest. The constitutively produced ( E )‐β‐caryophyllene on the other hand attracted both parasitoids and planthoppers, resulting in an increased herbivore load. Thus, silencing either signal resulted in specific insect assemblages in the field, highlighting the importance of plant volatiles in determining insect community structures. Moreover, the results imply that the manipulation of volatile emissions in crops has great potential for the control of pest populations.

Familial gastric cancer: guidelines for diagnosis, treatment and periodic surveillance - Irma Kluijt; Rolf H. Sijmons; Nicoline Hoogerbrugge; John T. Plukker; Daphne de Jong; J. Han van Krieken; Richard van Hillegersberg; Marjolijn Ligtenberg; Eveline Bleiker; Anemieke Cats (Familial Cancer, 2012)

Multi-scale Structural and Tensile Mechanical Response of Annulus Fibrosus to Osmotic Loading - Woojin M. Han; Nandan L. Nerurkar; Lachlan J. Smith; Nathan T. Jacobs; Robert L. Mauck; Dawn M. Elliott (Annals of Biomedical Engineering, 2012)

Rapid Determination of Mercury in Contaminated Soil and Plant Samples Using Portable Mercury Direct Analyzer without Sample Preparation, a Comparative Study - John G. Kelly; Fengxiang X. Han; Yi Su; Yunjun Xia; Valerie Philips; Zhiqi Shi; David L. Monts; Sergio T. Pichardo; Kang Xia (Water, Air, & Soil Pollution, 2012)

Inter-population comparisons of copper resistance and accumulation in the red seaweed, Gracilariopsis longissima - Murray T. Brown; James E. Newman; Taejun Han (Ecotoxicology, 2012)

Influence of salinity on metal toxicity to Ulva pertusa - Jeong-ju Oh; Eun-Mi Choi; Young-Seok Han; Jeong-Hyun Yoon; Areum Park; Kyosun Jin; Ju-Wook Lee; Hoon Choi; Sunjin Kim; Murray T. Brown; Taejun Han (Toxicology and Environmental Health Sciences, 2012)

Case report: a p.C618S RET proto-oncogene germline mutation in a large Chinese pedigree with familial medullary thyroid carcinoma - X.-P. Qi; R.-B. Ying; J.-M. Ma; W.-T. Liu; Z.-F. Du; J. Fei; C.-P. Yang; Q.-Z. Song; H.-Y. Jin; Z.-G. Chen; J.-S. Han; J.-Q. Wang; et al. (Familial Cancer, 2012)

Application of tyramide signal amplification‐fluorescence in situ hybridisation and flow cytometry to detection of Heterosigma akashiwo (Raphidophyceae) in natural waters - J Lee; T Katano; M Chang; M‐S Han (New Zealand Journal of Marine and Freshwater Research, 2012)
We developed protocols to analyse the cell cycle of Heterosigma akashiwo in the natural phytoplankton assemblage using tyramide signal amplification‐fluorescence in situ hybridisation (TSA‐FISH) and flow cytometry. We determined the optimum probe and formamide concentrations for the species‐specific TSA‐FISH probe to be 0.5 ng µL −1 and 40%, respectively. The probe did not hybridise to non‐target phytoplankton including Chattonella sp., which is closely related to Heterosigma and has high sequence similarity to it. We could successfully identify G1‐ and G2‐phase cells and the diel cell cycle of H. akashiwo not only in the laboratory but also in the field after TSA‐FISH. These results demonstrate that TSA‐FISH for H. akashiwo in natural coastal waters could serve as a powerful tool for understanding their bloom mechanism using flow cytometry.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Sensitivity of spore germination and germ tube elongation of Saccharina japonica to metal exposure - Taejun Han; Jeong-Ae Kong; Hee-Gyu Kang; Seon-Jin Kim; Gyo-Sun Jin; Hoon Choi; Murray T. Brown (Ecotoxicology, 2011)

Individual and combined effects of multiple pathogens on Pacific treefrogs - John M. Romansic; Pieter T. J. Johnson; Catherine L. Searle; James E. Johnson; Tate S. Tunstall; Barbara A. Han; Jason R. Rohr; Andrew R. Blaustein (Oecologia, 2011)

Smoking and alcohol drinking increased the risk of esophageal cancer among Chinese men but not women in a high-risk population - Ming Wu; Jin-Kou Zhao; Zuo-Feng Zhang; Ren-Qiang Han; Jie Yang; Jin-Yi Zhou; Xu-Shan Wang; Xiao-Feng Zhang; Ai-Min Liu; Pieter van’ t Veer; Frans J. Kok; Ellen Kampman (Cancer Causes & Control, 2011)

Engineering supported membranes for cell biology - Cheng-han Yu; Jay T. Groves (Medical & Biological Engineering & Computing, 2010)

Human Enteric Viruses in Groundwater - S. H. Park; E. J. Kim; T. H. Yun; J. H. Lee; C. K. Kim; Y. H. Seo; S. A. Oh; S. S. Choi; S. J. Cho; M. S. Kim; G. Y. Han; M. Y. Kim; et al. (Food and Environmental Virology, 2010)

Landscape‐scale analyses suggest both nutrient and antipredator advantages to Serengeti herbivore hotspots - T. Michael Anderson; J. Grant C. Hopcraft; Stephanie Eby; Mark Ritchie; James B. Grace; Han Olff (Ecology, 2010)
Mechanistic explanations of herbivore spatial distribution have focused largely on either resource‐related (bottom‐up) or predation‐related (top‐down) factors. We studied direct and indirect influences on the spatial distributions of Serengeti herbivore hotspots, defined as temporally stable areas inhabited by mixed herds of resident grazers. Remote sensing and variation in landscape features were first used to create a map of the spatial distribution of hotspots, which was tested for accuracy against an independent data set of herbivore observations. Subsequently, we applied structural equation modeling to data on soil fertility and plant quality and quantity across a range of sites. We found that hotspots in Serengeti occur in areas that are relatively flat and located away from rivers, sites where ungulates are less susceptible to predation. Further, hotspots tend to occur in areas where hydrology and rainfall create conditions of relatively low‐standing plant biomass, which, coupled with grazing, increases forage quality while decreasing predation risk. Low‐standing biomass and higher leaf concentrations of N, Na, and Mg were strong direct predictors of hotspot occurrence. Soil fertility had indirect effects on hotspot occurrence by promoting leaf Na and Mg. The results indicate that landscape features contribute in direct and indirect ways to influence the spatial distribution of hotspots and that the best models incorporated both resource‐ and predation‐related factors. Our study highlights the collective and simultaneous role of bottom‐up and top‐down factors in determining ungulate spatial distributions.

Changes in the frequency, scale, and failing areas of latest Quaternary (<29.4 cal. ka B.P.) slope failures along the SW Ulleung Basin, East Sea (Japan Sea), inferred from depositional characters of densely dated turbidite successions - Sang Hoon Lee; Jang J. Bahk; Han J. Kim; Kyung E. Lee; Hyeong T. Jou; Bong C. Suk (Geo-Marine Letters, 2010)

A novel single-nucleotide polymorphism of thevisfatin gene and its associations with performance traits in the chicken - R. L. Han; X. Y. Lan; L. Z. Zhang; G. Ren; Y. J. Jing; M. J. Li; B. Zhang; M. Zhao; Y. K. Guo; X. T. Kang; H. Chen (Journal of Applied Genetics, 2010)

Internal reflection pattern of Korea Strait shelf mud (Nakdong River subaqueous delta) off southeast Korea and implications for Holocene relative base‐level change - Gwang H. Lee; Dae C. Kim; Mi K. Park; Soo C. Park; Han J. Kim; Hyeong T. Jou; Boo K. Khim (Island Arc, 2010)
The Korea Strait shelf mud (KSSM) (Nakdong River subaqueous delta) is the most conspicuous Holocene sedimentary feature in the inner shelf off southeast Korea. Analysis of multi‐channel sparker profiles and 14 C ages of sediment cores reveals that the KSSM consists of three seismic units at the depocenter (>60 m thick): (i) the thin transgressive bottom (> ca 8000 cal bp ); (ii) thick (>40 m) obliquely progradational middle ( ca 8000– ca 2600 cal bp ); and (iii) thin transgressive top ( ca 2600 cal bp –present) units. The relative base level, predicted from the internal reflection pattern of the KSSM, remained significantly deeper (up to >70 m) than global sealevel during much of the Holocene. The apparent gradual drop (∼20 m) of the relative base level during the deposition of the middle unit, followed by a rise, further suggests that base level does not conform to sealevel and is more sensitive than the relative sealevel is to the local oceanographic regime and processes.

Analysis of genetic structure and relationship among nine indigenous Chinese chicken populations by the Structure program - H. F. Li; W. Han; Y. F. Zhu; J. T. Shu; X. Y. Zhang; K. W. Chen (Journal of Genetics, 2009)

Estimation of the gross primary production of an old‐growth temperate mixed forest using eddy covariance and remote sensing - J. B. Wu; X. M. Xiao; D. X. Guan; T. T. Shi; C. J. Jin; S. J. Han (International Journal of Remote Sensing, 2009)

Landscape Planning for Agricultural Nonpoint Source Pollution Reduction III: Assessing Phosphorus and Sediment Reduction Potential - Matthew W. Diebel; Jeffrey T. Maxted; Dale M. Robertson; Seungbong Han; M. Jake Vander Zanden (Environmental Management, 2009)

Inhibition of the development of collagen-induced arthritis in Wistar rats through vagus nerve suspension: a 3-month observation - P. Zhang; D. Han; T. Tang; X. Zhang; K. Dai (Inflammation Research, 2008)

Suggestion of Potential Stent Design Parameters to Reduce Restenosis Risk driven by Foreshortening or Dogboning due to Non-uniform Balloon-Stent Expansion - Dohyung Lim; Seung-Kwan Cho; Won-Pil Park; Anders Kristensson; Jai-Young Ko; S. T. S. Al-Hassani; Han-Sung Kim (Annals of Biomedical Engineering, 2008)

Identification of a recombinant dengue virus type 1 with 3 recombination regions in natural populations in Guangdong province, China - S.-P. Chen; M. Yu; T. Jiang; Y.-Q. Deng; C.-F. Qin; J.-F. Han; E.-D. Qin (Archives of Virology, 2008)

Radiation-Guided P-Selectin Antibody Targeted to Lung Cancer - G. Hariri; Y. Zhang; A. Fu; Z. Han; M. Brechbiel; M. N. Tantawy; T. E. Peterson; R. Mernaugh; D. Hallahan (Annals of Biomedical Engineering, 2008)

Use of bioluminescent imaging to investigate the role of nuclear factor-κΒ in experimental non-small cell lung cancer metastasis - Georgios T. Stathopoulos; Taylor P. Sherrill; Wei Han; Ruxana T. Sadikot; Vasiliy V. Polosukhin; Barbara Fingleton; Fiona E. Yull; Timothy S. Blackwell (Clinical & Experimental Metastasis, 2008)

A novel gene, Pi40(t), linked to the DNA markers derived from NBS-LRR motifs confers broad spectrum of blast resistance in rice - J. U. Jeung; B. R. Kim; Y. C. Cho; S. S. Han; H. P. Moon; Y. T. Lee; K. K. Jena (Theoretical and Applied Genetics, 2007)

Utilization of seagrass habitats by juvenile groupers and snappers in Banten Bay, Banten Province, Indonesia - Siti Nuraini; Eira C. Carballo; Wim L. T. van Densen; Marcel A. M. Machiels; Han J. Lindeboom; Leopold A. J. Nagelkerke (Hydrobiologia, 2007)

Monitoring of Aerial Pollutants Emitted from Swine Houses in Korea - Ki Y. Kim; Han J. Ko; Hyeon T. Kim; Yoon S. Kim; Young M. Roh; Cheol M. Lee; Chi N. Kim (Environmental Monitoring and Assessment, 2007)

Gene expression profiling reveals two separate mechanisms regulating apoptosis in rectal carcinomas in vivo - Elza C. de Bruin; Simone van de Pas; Cornelis J. H. van de Velde; J. Han J. M. van Krieken; Lucy T. C. Peltenburg; Corrie A. M. Marijnen; Jan Paul Medema (Apoptosis, 2007)

Surveying sandy deserts and desertified lands in north‐western China by remote sensing - C. Z. Yan; T. Wang; Z. W. Han; Y. F. Qie (International Journal of Remote Sensing, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Estimating afternoon MODIS land surface temperatures (LST) based on morning MODIS overpass, location and elevation information - N. C. Coops; D. C. Duro; M. A. Wulder; T. Han (International Journal of Remote Sensing, 2007)

Approaching chickpea quantitative trait loci conditioning resistance to Ascochyta rabiei via comparative genomics - X. Y. Bian; R. Ford; T. R. Han; T. E. Coram; E. C. K. Pang; P. W. J. Taylor (Australasian Plant Pathology, 2007)

Removal of Alachlor and Pretilachlor by Laboratory-Synthesized Zerovalent Iron in Pesticide Formulation Solution - H. Y. Kim; I. K. Kim; J. H. Shim; Y.-C. Kim; T.-H. Han; K.-C. Chung; P. I. Kim; B.-T. Oh; I. S. Kim (Bulletin of Environmental Contamination and Toxicology, 2006)

Cloning of ATP‐dependent protease ClpXP genes in Aeromonas veronii - H‐J Han; H Kondo; G Vivekanandhan; I Hirono; T Aoki (Journal of Fish Diseases, 2006)

Using canopy reflectance and partial least squares regression to calculate within-field statistical variation in crop growth and nitrogen status of rice - Hung T. Nguyen; Jun Han Kim; Anh T. Nguyen; Lan T. Nguyen; Jin Chul Shin; Byun-Woo Lee (Precision Agriculture, 2006)

Antidepressant-like effects of PDE4 inhibitors mediated by the high-affinity rolipram binding state (HARBS) of the phosphodiesterase-4 enzyme (PDE4) in rats - Han-Ting Zhang; Yu Zhao; Ying Huang; Chengjun Deng; Allen T. Hopper; Michael De Vivo; Gregory M. Rose; James M. O’Donnell (Psychopharmacology, 2006)

Pioglitazone, a synthetic ligand for PPARγ, induces apoptosis in RB-deficient human colorectal cancer cells - C. J. Lee; J. S. Han; C. Y. Seo; T. H. Park; H. C. Kwon; J. S. Jeong; I. H. Kim; J. Yun; Y. S. Bae; J. Y. Kwak; J. I. Park (Apoptosis, 2006)

Delineating the northern part of the Socotra Basin, offshore Korea, using marine magnetics - M. Suh; T. F. Abdallatif; J. Han; S. Choi; J. Oh (Geo-Marine Letters, 2005)

A genetic linkage map for azuki bean [Vigna angularis (Willd.) Ohwi & Ohashi] - O. K. Han; A. Kaga; T. Isemura; X. W. Wang; N. Tomooka; D. A. Vaughan (Theoretical and Applied Genetics, 2005)

The influence of muscle type and dystrophin deficiency on murine expression profiles - Judith N. Haslett; Peter B. Kang; Mei Han; Alvin T. Kho; Despina Sanoudou; Jay M. Volinski; Alan H. Beggs; Isaac S. Kohane; Louis M. Kunkel (Mammalian Genome, 2005)

Vestibular and non-vestibular contributions to eye movements that compensate for head rotations during viewing of near targets - Yanning H. Han; Arun N. Kumar; Millard F. Reschke; Jeffrey T. Somers; Louis F. Dell’Osso; R. John. Leigh (Experimental Brain Research, 2005)

Effects of the novel PDE4 inhibitors MEM1018 and MEM1091 on memory in the radial-arm maze and inhibitory avoidance tests in rats - Han-Ting Zhang; Ying Huang; Neesha U. Suvarna; Chengjun Deng; Alicia M. Crissman; Allen T. Hopper; Michael De Vivo; Gregory M. Rose; James M. O’Donnell (Psychopharmacology, 2005)

Genetic mapping of EST-derived microsatellites from the diploid Gossypium arboreum in allotetraploid cotton - Z.-G. Han; W.-Z. Guo; X.-L. Song; T.-Z. Zhang (Molecular Genetics and Genomics, 2004)

Use of Pi5(t) markers in marker-assisted selection to screen for cultivars with resistance to Magnaporthe grisea - G. Yi; S.-K. Lee; Y.-K. Hong; Y.-C. Cho; M.-H. Nam; S.-C. Kim; S.-S. Han; G.-L. Wang; T.-R. Hahn; P.C. Ronald; J.-S. Jeon (Theoretical and Applied Genetics, 2004)

Experimental investigation of the mammary gland tumour phantom for multifrequency microwave radio-thermometers - J. W. Lee; S. M. Lee; K. S. Kim; W. T. Han; G. Yoon; L. A. Pasmanik; I. A. Ulyanichev; A. V. Troitsky (Medical & Biological Engineering & Computing, 2004)

Characteristics of Ion Components and Trace Elements of Fine Particles at Gosan, Korea in Spring time from 2001 to 2002 - J. S. Han; K. J. Moon; J. Y. Ahn; Y. D. Hong; Y. J. Kim; S. Y. Ryu; S. S. Cliff; T. A. Cahill (Environmental Monitoring and Assessment, 2004)

Characterization of genotype II Rubella virus strains - D.-P. Zheng; Y. M. Zhou; K. Zhao; Y.-R. Han; T. K. Frey (Archives of Virology, 2003)

Nucleotide sequence and taxonomy of Cycas necrotic stunt virus - S. S. Han; A. V. Karasev; H. Ieki; T. Iwanami (Archives of Virology, 2002)

The exotic American eel in Taiwan: ecological implications - Y.‐S. Han; C.‐H. Yu; H.‐T. Yu; C.‐W. Chang; I‐C. Liao; W.‐N. Tzeng (Journal of Fish Biology, 2002)
Six American eels Anguilla rostrata were identified in the Kaoping River of south‐western Taiwan by sequencing the mitochondrial cytochrome b gene ( mtCyt‐b ). This was the first record of an exotic eel species in the natural waters of Taiwan. The exotic eels may have been imported from North America at the elver stage for aquaculture and escaped from culture ponds.

Environmental fate of the triazole fungicide propiconazole in a rice-paddy-soil lysimeter - In Seon Kim; Lee A. Beaudette; Jae Han Shim; Jack T Trevors; Yong Tack Suh (Plant and Soil, 2002)

Nucleotide sequence of a Japanese isolate of Squash mosaic virus - S. S. Han; K. Yoshida; A. V. Karasev; T. Iwanami (Archives of Virology, 2002)

Complex control of the developmental regulatory locus brlA in Aspergillus nidulans - S. Han; T. Adams (Molecular Genetics and Genomics, 2001)

Sequence diversity and interrelationships among isolates of satsuma dwarf-related viruses - T. Iwanami; Y. Kondo; M. Kobayashi; S. S. Han; A. V. Karasev (Archives of Virology, 2001)

Amphitrite ornata, a Marine Worm, Contains Two Dehaloperoxidase Genes - Kaiping Han; Sarah A. Woodin; David E. Lincoln; Kevin T. Fielman; Bert Ely (Marine Biotechnology, 2001)

Host effect on genetic variation of Marssonina brunnea pathogenic to poplars - Z. M. Han; T. M. Yin; C. D. Li; M. R. Huang; R.L. Wu (Theoretical and Applied Genetics, 2000)

Ionizing radiation stimulates octamer factor DNA binding activity in human carcinoma cells - Rachel L. Meighan-Mantha; Anna T. Riegel; Simeng Suy; Violaine Harris; Fuh-Han Wang; Christopher Lozano; Theresa L. Whiteside; Usha Kasid (Molecular and Cellular Biochemistry, 1999)

An ensemble forecast of the South China Sea monsoon - T. N. Krishnamurti; Mukul Tewari; Ed Bensman; Wei Han; Zhan Zhang; William K. M. Lau (Advances in Atmospheric Sciences, 1999)

Increased mRNAs for procollagens and key regulating enzymes in rat skeletal muscle following downhill running - Xiao-Yan Han; W. Wang; Satu O. A. Koskinen; Vuokko Kovanen; T. E. S. Takala; Jyrki Komulainen; Veikko Vihko; Philip C. Trackman (Pflügers Archiv - European Journal of Physiology, 1999)

Optimization of AFLP fingerprinting of organisms with a large-sized genome: a study on Alstroemeria spp. - T. H. Han; H. J. van Eck; M. J. De Jeu; E. Jacobsen (Theoretical and Applied Genetics, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Estimation of Target Hazard Quotients and Potential Health Risks for Metals by Consumption of Seafood in Taiwan - B.-C. Han; W. L. Jeng; R. Y. Chen; G. T. Fang; T. C. Hung; R. J. Tseng (Archives of Environmental Contamination and Toxicology, 1998)

Interleukin-13 increases prostaglandin E2 (PGE2) production by normal human polymorphonuclear neutrophils by enhancing cyclooxygenase 2 (COX-2) gene expression - C.-L. Yu; M.-H. Huang; Y.-Y. Kung; C.-Y. Tsai; Y.-Y. Tsai; S.-T. Tsai; D.-F. Huang; K.-H. Sun; S.-H. Han; H.-S. Yu (Inflammation Research, 1998)

Organization of convection and monsoon forecasts - T. N. Krishnamurti; H. S. Bedi; Wei Han (Meteorology and Atmospheric Physics, 1998)

Sensitivity of hurricane intensity forecasts to physical initialization - T. N. Krishnamurti; Wei Han; D. Oosterhof (Meteorology and Atmospheric Physics, 1998)

Rock-Shells ( Thais clavigera ) as an Indicator of As, Cu, and Zn Contamination on the Putai Coast of the Black-Foot Disease Area in Taiwan - B. C. Han; W. L. Jeng; M. S. Jeng; L. T. Kao; P. J. Meng; Y. L. Huang (Archives of Environmental Contamination and Toxicology, 1997)

Effect of EHS matrix on expression of transgenes in HC11 cells - T. H. Lee; M. G. Baik; W. B. Im; C. S. Lee; Y. M. Han; S. J. Kim; K. K. Lee; Y. J. Choi (In Vitro Cellular & Developmental Biology - Animal, 1997)

Human Papillomavirus is More Prevalent in First Trimester Spontaneously Aborted Products of Conception Compared to Elective Specimens - P L Hermonat; L Han; P J Wendel; J G Quirk; S Stern; C L Lowery; T M Rechtin (Virus Genes, 1997)

Nucleotide sequence of the human? 1-globin gene - J. M. Gonzalez-Redondo; I. S. Han; Y. -C. Gu; T. H. J. Huisman (Biochemical Genetics, 1988)

Effect of growth condition on enzymes of the citric acid cycle and the glyoxylate cycle in the photosynthetic bacterium Rhodopseudomonas palustris - J. H. Eley; K. Knobloch; T. -W. Han (Antonie van Leeuwenhoek, 1979)